Multiple weak supramolecular interactions stabilize a surprisingly twisted As2L3 assembly - Pitt, Melanie A.; Zakharov, Lev N.; Vanka, Kumar; Thompson, Ward H.; Laird, Brian B.; Johnson, Darren W. (Chemical Communications, 2008)
A combined crystallographic, DFT and NMR spectroscopic study of a flexible As(2)(3) assembly reveals temperature dependent conformational behavior in solution and a highly asymmetric structure stabilized by As-pi and edge-to-face aromatic interactions.

Multipoint anchoring of the [2.2.2.2]metacyclophane motif to a gold surface via self-assembly: coordination chemistry of a cyclic tetraisocyanide revisited - Toriyama, Masaharu; Maher, Tiffany R.; Holovics, Thomas C.; Vanka, Kumar; Day, Victor W.; Berrie, Cindy L.; Thompson, Ward H.; Barybin, Mikhail V. (Inorganic Chemistry, 2008)
A one-pot transformation of bis(2-isocyano-3-methylphenyl)ethane affords gram quantities of 8,16,24,32-tetraisocyano[2.2.2.2]metacyclophane ( 3). The solid state structure of 3 is remarkably close to the lowest energy conformation found on the potential energy landscape for 3 by DFT. In solution, the structure of metacyclophane 3 is mobile but can be locked in a rectangular gauche- anti- gauche- anti conformation by coordination of the isocyanide substituents to the [W(CO) 5] units to give [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) ( 5). The tetranuclear [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) motif featured in crystallographically characterized 5 may be present in several insoluble complexes of 3 previously described as mononuclear eta (4) species. A self-assembled monolayer of metacyclophane 3 is formed upon exposing a solution of 3 to the gold(111) surface with no precautions to exclude air or light. The monolayer nature of the film was confirmed by optical ellipsometry. The isocyanide stretching band for 3 shifts from 2119 cm (-1) in solution to 2175 cm (-1) upon chemisorption to metallic gold. The FTIR spectrum of the film indicates interaction of 3 with the gold surface via all four of its isocyanide anchors. No gold-facilitated oxidation of the -NC junctions was detected under ambient conditions. The energy cost associated with accessing the conformations of 3 suitable for mu 4-eta (1):eta (1):eta (1):eta (1) interaction of the molecule with the Au(111) surface is under 8 kcal/mol, a value that can be easily offset by formation of a gold-isocyanide bond. Two different mu 4-eta (1):eta (1):eta (1):eta (1) coordination arrangements of 3 with respect to gold atoms on the (111) face of the fcc Au lattice are suggested.

Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

DFT Study of lewis base interactions with the MgCl2 surface in the ziegler-natta catalytic system: expanding the role of the donors - Vanka, Kumar; Singh, Gurmeet; Iyer, Divya; Gupta, Virendra K. (Journal of Physical Chemistry C, 2010)
We present a computational study, using density functional theory, of the role of internal and external donors in supported heterogeneous Ziegler-Natta polymerization catalyst systems. The focus of the investigation is the ability of the donors to stabilize the MgCl2 support through the zip mode of coordination. Phthalates and alkoxy benzoates have been considered as representative internal and external donors, respectively. Models for the alpha (ccp) and the beta (hcp) phases of the (110) MgCl2 lateral cut have been considered. Studies were first done with a ``Fully Fixed Model'', where the atoms in the MgCl2 lateral cuts were kept fixed. The studies indicated that the phthalate donors would preferentially stabilize the alpha phase of MgCl2, while the alkoxy benzoate donors would stabilize the beta phase more, corroborating experimental results. A comparison of the zip coordination mode with other modes of coordination (mono, chelate, and bridge) indicates that it would be preferred over the mono and chelate coordination modes and be competitive with the bridge coordination mode. The validity of the Fully Fixed Model was then tested by doing calculations with the Partially Relaxed (some of the magnesium and chlorine atoms unfixed) and the Fully Relaxed (all atoms free) Models. The results from the latter two models corrected some of the discrepancies that had been observed for the Fully Fixed Model in comparison to previous experimental and computational investigations but were in general agreement with the Fully Fixed Model, indicating that the overall conclusions drawn with the earlier model are correct. Insertion studies done on an octahedrally coordinated titanium site flanked by two zip-coordinated phthalate donor molecules indicated that the zip-coordinating donors can confer exceptional regioselectivity to the titanium center. A list of potential donors that could serve as external donors, with di-iso-butyl phthalate (DIBP) as the internal donor, was investigated, and it was found that 1,3-diethers would serve as the best external donors to DIBP.

Structural diversity in partially fluorinated metal organic frameworks (F-MOFs) composed of divalent transition metals, 1,10-phenanthroline, and fluorinated carboxylic acid - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Vanka, Kumar; Banerjee, Rahul (Crystal Growth & Design, 2010)
Seven new partially fluorinated metal-organic frameworks (F-MOFs) have been synthesized under different solvothermal conditions (H(2)O or N,N-dimethylformamide (DMF)) from transition metal cations [Zn(II), Co(II), and Mn(II)], 1,10-phenanthroline (phen), and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) to determine the influence of reaction conditions on the formation of metal-organic frameworks. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. Of the seven materials, two contain three-dimensional connectivity: Co(3)(hfbba)(6)(phen)(2) (F-MOF-6) and Mn(3)(hfbba)(6)(Phen)(2) (F-MOF-10). Three materials are one-dimensional structures: Zn(hfbba)(0.5)(phen)(HCO(2)) (F-MOF-8), Mn(Hhfbba)(2)(Phen) (F-MOF-11), and [Mn(hfbba)(2)(dm-phen)]center dot(H(2)O) (F-MOF-11A). Lastly, Co(hfbba)(phell)(2)center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-7) and Zn(hfbba)(phen)(2)center dot 2(H(2)hfbba) (H(2)O)-(HCO(2)) (F-MOF-9) are discrete zero-dimensional molecular complexes. F-MOF-6 and -10, which feature it three-dimensional (3D) framework with pcu topolgy are formed in DMF like F-MOF-8 and at 85 degrees C. The remaining F-MOFs are formed by a solvothermal reaction at 120 degrees C in water. F-MOF-7 and -9 are isostructural discrete zero-dimensional molecular complexes (a similar to 19.5; b similar to 13.7; c similar to 26.2/29.6 angstrom; beta similar to 99.9/120.04; V similar to 6840 angstrom(3)). All these F-MOFs were structurally determined by single-crystal X-ray diffraction. Solid-state properties such its UV-vis and the thermal stability of F-MOF-6 to -11A have also been studied. Insight into the factors influencing the preferred crystallization of a specific complex over others has been obtained from full quantum chemical (QM) calculations using density functional theory (DFT).

DFT investigation of the potential of porous cages for the catalysis of ammonia borane dehydrogenation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2011)
Full DFT based quantum mechanical studies reveal that zero dimensional porous structures, especially the newly proposed phosphorus incorporated organic cages, can be excellent catalysts for the dehydrogenation of ammonia borane.

Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate

Computational investigation of the role of the iridium dihydrogen pincer complex in the formation of the cyclic pentamer (NH2BH2)(5) - Ghatak, Kamalika; Vanka, Kumar (Computational and Theoretical Chemistry, 2012)
Computational studies with density functional theory (DFT) and MP2 have been done to investigate the interaction between the iridium dihydrogen pincer complex: (POCOP)IrH2 (where POCOP = eta(3)-1,3(OPt-Bu-2)(2)C6H3) and NH2BH2, the immediate product of ammonia borane (NH3BH3) dehydrogenation. A mechanism has been proposed for an oligomerisation process at the metal centre that involves competition between (i) insertion of an NH2BH2 molecule into the (NH2BH2)(n) chain and (ii) termination of the chain leading to the formation of the cyclic (NH2BH2)(n) oligomer. The calculated Delta G values show that the competition favours insertion over termination for the cases n = 1 to n = 4 but favours termination for n = 5. The computational studies therefore indicate that the cyclic pentamer (NH2BH2)(5) would be formed during NH3BH3 dehydrogenation by the (POCOP)IrH2 catalyst, agreeing with experimental findings. The mechanistic understanding gained has implications for the facile regeneration of ammonia borane. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ammonia borane; Hydrogen storage; Iridium pincer ligand catalyst; Mechanistic studies; Oligomerisation cycle

Exploring the potential of doped zero-dimensional cages for proton transfer in fuel cells: a computational study - Mane, Manoj V.; Venkatnathan, Arun; Ghatak, Kamalika; Vanka, Kumar (Journal of Physical Chemistry B, 2012)
Calculations with density functional theory (DFT) and MP2 have been done to investigate the potential of recently synthesized durable zero-dimensional (OD) nitrogen-based cage structures to perform as efficient proton-exchange membranes (PEMs) in fuel cells. Our calculations suggest that the hydrogenated 0-D cages, in combination with hydrogen-bonding 1,2,3- and 1,2,4-triazole molecules, would perform as highly efficient PEMs. The results are important in the context of the need for efficient PEMs for fuel cells, especially at higher temperatures (greater than 120 degrees C) where conventional water-based PEMs such as Nafion have been found to be ineffective.

New approximate method for the stochastic simulation of chemical systems: the representative reaction approach - Kadam, Shantanu; Vanka, Kumar (Journal of Computational Chemistry, 2012)
We have developed two new approximate methods for stochastically simulating chemical systems. The methods are based on the idea of representing all the reactions in the chemical system by a single reaction, i.e., by the representative reaction approach (RRA). Discussed in the article are the concepts underlying the new methods along with flowchart with all the steps required for their implementation. It is shown that the two RRA methods {with the reaction \$ 2A \textbackslashrightarrow B \$ as the representative reaction (RR)} perform creditably with regard to accuracy and computational efficiency, in comparison to the exact stochastic simulation algorithm (SSA) developed by Gillespie and are able to successfully reproduce at least the first two moments of the probability distribution of each species in the systems studied. As such, the RRA methods represent a promising new approach for stochastically simulating chemical systems. (C) 2011 Wiley Periodicals, Inc. J Comput Chem, 2012
Keywords: approximate algorithm; Stochastic simulations

Radical mediated deoxygenation of inositol benzylidene acetals: conformational analysis, DFT calculations, and mechanism - Gurale, Bharat P.; Vanka, Kumar; Shashidhar, Mysore S. (Carbohydrate Research, 2012)
Xanthates of 1,3-benzylidene acetal derivatives of myo- and neo-inositols undergo dideoxygenation under Barton-McCombie conditions, as a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Scrutiny of structure of these bicyclic inositol derivatives shows that although the conformation of the two rings can vary depending on the configuration of the inositol ring and the phase in which the molecules are present, both the xanthates lead to the formation of the same dideoxyinositol. DFT calculations on these molecular systems suggest that neo-inositol derivatives undergo conformational change prior to radical formation while myo- inositol derivatives undergo conformational change subsequent to radical formation, during the deoxygenation reaction. A low barrier for intramolecular hydrogen transfer supports the extreme facility of this deoxygenation reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Deoxygenation; DFT; Inositol; Mechanism; Radical; Xanthate

Theoretical study of metal-metal cooperativity in the homogeneous water gas shift reaction - Kuriakose, Nishamol; Kadam, Shantanu; Vanka, Kumar (Inorganic Chemistry, 2012)
The possibility of metal-metal cooperativity in improving the yield of the homogeneous water gas shift reaction (WGSR) has been investigated through full quantum mechanical density functional theory calculations. The calculations indicate that bimetallic catalysts would be likely to be more highly active than mononuclear metal-based catalysts for the WGSR. The results have implications for the design of improved WGSR catalysts in the future.

Can molecular cages be effective at small molecule activation? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Inorganic Chemistry, 2013)
Several approaches have been investigated in recent years in the area of small molecule activation. The current work introduces a new concept in this field: that of molecular cages, containing only main group elements, serving to activate small molecules. Full quantum mechanical calculations employing DFT/SCS-MP2 methods indicate that recently synthesized Ga-N cage compounds would be excellent candidates for mediating in important reactions such as the catalysis of ammonia borane dehydrogenation. The current work therefore opens up exciting new possibilities in small molecule activation research.

Catalytic and DFT study of selective ethylene oligomerization by nickel(II) oxime-based complexes - Tayade, Kamlesh N.; Mane, Manoj V.; Sen, Suman; Murthy, C. N.; Tembe, Gopal L.; Pillai, S. Muthukumaru; Vanka, Kumar; Mukherjee, Soumen (Journal of Molecular Catalysis A-Chemical, 2013)
The reactivity of nickel(II) thiophenealdoxime complex (3) toward oligomerization of ethylene in the presence of an alkylaluminum co-catalyst has been studied. The complex was found to be a selective ethylene dimerization catalyst in the presence of co-catalysts such as methylalumoxane (MAO) and diethylaluminum chloride (DEAC). With DEAC, the productivity was considerably higher than with MAO. Under optimum conditions the productivity reaches 388 kg/mol catalyst/h/bar with DEAC whereas for MAO this value was 119 kg/mol catalyst/h/bar. Complex 3 displays good ethylene conversions of up to a maximum of 90% with exceptionally high alpha-selectivity for 1-butene (>99.5%) amongst C-4 products. Computational studies using density functional theory (DFT) were also carried out to ascertain the decomposition pathway for 3 as well as that for Ni(II) complex of the pyridine ketoxime ligand 2. The results suggest that loss of one of the two bidentate oxime ligands attached to the metal center through reaction with DEAC is likely for both 2 and 3. Further, calculations indicate that the subsequent decomposition step was significantly more probable for 3 than for 2 thus explaining why the pyridine ketoxime ligand bound nickel complex 2 was experimentally found to be more stable than the thiophene aldoxime bound nickel complex 3. Calculations also show that the proton of the -OH group (oxime) plays a major role in the stability of the molecules. This was confirmed experimentally by synthesizing the Ni(II) dichloro complex of Pyridine-2-carbaldehyde O-methyloxime 5 and reacting it with ethylene under similar conditions. 5 was found to be highly active even at low co-catalyst concentrations. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Butene-1; Ethylene dimerization; Ni(II) complex; Thiophene aldoxime

Exploring the effectiveness of different Lewis pair combinations in caged structures for the catalysis of ammonia borane dehydrogenation: a DFT study - Pal, Amrita; Vanka, Kumar (Physical Chemistry Chemical Physics, 2013)
Zero dimensional cage structures containing four phenyl rings separated by imine linkers have recently been synthesized. In the current work, through a computational investigation using density functional theory (DFT), we demonstrate that modifying such cages by replacing the 2, 4, 6 carbon atoms in the phenyl rings to yield new rings, as well as replacing the imine moiety in the linker by other electronegative atoms, can yield interesting new cages that can be reactive in catalysing reactions such as the dehydrogenation of ammonia borane-an important reaction in hydrogen storage research. Specifically, it is predicted that phosphorus-nitrogen pairs (phosphorus in the 2, 4, 6 positions in the ring, nitrogen in the linker position), germanium-nitrogen and germanium-phosphorus pair combinations would lead to effective Lewis pairs that can work in tandem to dehydrogenate ammonia borane efficiently under room temperature conditions.

GIAO/DFT studies on 1,2,4-triazole-5-thiones and their propargyl derivatives - Phalgune, Usha D.; Vanka, Kumar; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2013)
Density functional theory (DFT)/Becke-Lee-Yang-Parr (B3LYP) and gauge-including atomic orbital (GIAO) calculations were performed on a number of 1,2,4-triazole derivatives, and the optimized structural parameters were employed to ascertain the nature of their predominant tautomers. C-13 and N-15 NMR chemical shifts of 3-substituted 1,2,4-triazole-5-thiones and their propargylated derivatives were calculated via GIAO/DFT approach at the B3LYP level of theory with geometry optimization using a 6-311++G** basis set. A good agreement between theoretical and experimental C-13 and N-15 NMR chemical shifts could be found for the systems investigated. The data generated were useful in predicting N-15 chemical shifts of all the nitrogen atoms of the triazole ring, some of which could not be obtained in solution state N-15 HMBC/HSQC NMR measurements. The energy profile computed for the dipropargylated derivatives was found to follow the product distribution profile of regioisomers formed during propargylation of 1,2,4-triazole thiones. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: 1; 2; 4-triazole-5-thiones; C-13; DFT; GIAO; N-15; NMR; Regioisomers; tautomers

Metal or nonmetal cooperation with a phenyl group: route to catalysis? a computational investigation - Ghatak, Kamalika; Mane, Manoj; Vanka, Kumar (ACS Catalysis, 2013)
Full quantum mechanical calculations demonstrate that cooperativity in the form of the activation of the M-C bond (M: transition metal or boron, C: the ipso carbon of the coordinated phenyl group) can lead to effective catalysis pathways. Calculations show that the presence of an aromatic bidentate ligand attached to a transition metal, or even a main group element, such as boron, can lead to effective catalysts for,a, range of important reactions, such as the dehydrogenation of ammonia borane and formic acid and the activation of the N-H, bond in aromatic amities. Moreover, it is shown that the design of tridentate pincer complexes with the aromatic group at a terminal end can lead to effective M-C cooperativity. As such, the current work introduces a new concept in cooperativity and bond activation chemistry.
Keywords: catalysis; Density functional theory; metal-ligand cooperativity; small molecule activation

Proposing late transition metal complexes as frustrated Lewis pairs - a computational investigation - Pal, Amrita; Vanka, Kumar (Dalton Transactions, 2013)
There has been considerable interest in recent times to develop transition metal complex systems that can demonstrate metal-ligand cooperativity. It has recently been shown (Wass et al., J. Am. Chem. Soc., 2011, 133, 18463) that early transition metals can cooperate with ligands carrying phosphines as pendant groups, working as metal analogues to frustrated Lewis pairs (FLPs) to mediate in a variety of important reactions. What the current work attempts to do is to show how this concept of metal containing FLPs can be expanded to include late transition metal complexes as well: complexes that have been modified from existing systems that serve as efficient catalysts for homogeneous polymerization. A modified palladium complex has been considered in this regard as an example of a potential late transition metal FLP and studied with full quantum mechanical calculations. The calculations indicate that this complex would be effective at catalyzing ammonia borane dehydrogenation. The possibility of competing side reactions such as reductive elimination have also been considered, and it has been found that such processes would also yield stable products which could act as an FLP in catalyzing reactions such as the dehydrogenation of ammonia borane. The current work therefore expands the scope of metal containing FLPs to include late transition metals and demonstrates computationally the potential of such complexes for exhibiting metal-ligand cooperativity.

Solving the problem of negative populations in approximate accelerated stochastic simulations using the representative reaction approach - Kadam, Shantanu; Vanka, Kumar (Journal of Computational Chemistry, 2013)
Methods based on the stochastic formulation of chemical kinetics have the potential to accurately reproduce the dynamical behavior of various biochemical systems of interest. However, the computational expense makes them impractical for the study of real systems. Attempts to render these methods practical have led to the development of accelerated methods, where the reaction numbers are modeled by Poisson random numbers. However, for certain systems, such methods give rise to physically unrealistic negative numbers for species populations. The methods which make use of binomial variables, in place of Poisson random numbers, have since become popular, and have been partially successful in addressing this problem. In this manuscript, the development of two new computational methods, based on the representative reaction approach (RRA), has been discussed. The new methods endeavor to solve the problem of negative numbers, by making use of tools like the stochastic simulation algorithm and the binomial method, in conjunction with the RRA. It is found that these newly developed methods perform better than other binomial methods used for stochastic simulations, in resolving the problem of negative populations. (C) 2012 Wiley Periodicals, Inc.
Keywords: approximate methods; binomial distributions; Gillespie algorithm; Kinetic Monte Carlo; Poisson distributions; representative reaction approach; Stochastic simulations

Synthesis of palmyrolide A and its cis-isomer and mechanistic insight into trans-cis isomerisation of the enamide macrocycle - Philkhana, Satish Chandra; Seetharamsingh, B.; Dangat, Yuvraj B.; Vanka, Kumar; Reddy, D. Srinivasa (Chemical Communications, 2013)
Concise and protecting-group free synthesis of ent-palmyrolide A and (-)-cis-palmyrolide A were achieved starting from commercially available (S)-citronellal. The key fragment of palmyrolide A, ``(5S,7S)-7-hydroxy-5,8,8-trimethylnonanamide'', which makes up the most challenging part of the target molecule, was prepared in just three steps. A plausible mechanism for the trans-cis isomerization of the double bond in the macrocycle has been investigated.

1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU): a highly efficient catalyst in glycerol carbonate synthesis - Munshi, Mudassir K.; Gade, Swapna M.; Mane, Manoj V.; Mishra, Deepti; Pal, Sourav; Vanka, Kumar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Molecular Catalysis A-Chemical, 2014)
Transesterification of dimethyl carbonate (DMC) with glycerol (GLY) was investigated using various amines as catalysts. Amidines like 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) were found to be the best catalysts for this reaction. Best results: 98% conversion of GLY with 96% selectivity to GC (TON: 9408), were obtained with DBU as a catalyst. Effect of various reaction conditions on activity and selectivity were investigated using DBU as catalyst. The mechanism of the reaction was investigated with the help of H-1, C-13 and N-15 NMR analysis and OFT calculations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DBU; Glycerol; Glycerol carbonate; transesterification

Accounting of noise to solve the problem of negative populations in approximate accelerated stochastic simulations - Kadam, Shantanu; Vanka, Kumar (RSC Advances, 2014)
The advent of different approximate accelerated stochastic simulation methods has helped considerably in reducing the computational load of the exact simulation algorithms. However, along with the reduction in the computational load comes the risk of driving the molecular numbers to the regime of negative numbers during the simulations. Over the years, various methods have been developed in order to solve the problem by using different strategies. Some methods have employed binomial numbers to model the reactions, while others have tried the partitioning of the reaction network. In this manuscript, we have proposed a new approach where the noise inherent in the choice of the number of firings of a given reaction during a time step is taken into account. This idea of noise accounting is used in conjunction with the accelerated stochastic method: the Representative Reaction Approach (RRA). It is found that the new method is successful at solving the problem of negative numbers, and compares very favorably with other state-of-the-art stochastic simulation methods.

Asymmetric transfer hydrogenation of imines in water/methanol co-solvent system and mechanistic investigation by DFT study - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kuriakose, Nishamol; Vanka, Kumar; Kelkar, Ashutosh A. (RSC Advances, 2014)
Asymmetric transfer hydrogenation of various cyclic imines proceeded efficiently with water/methanol co-solvent media in 20 min with excellent yields and enantioselectivities by employing Rh-TsDPEN catalyst and sodium formate as a hydrogen donor. The role of the co-solvent in enhanced productivity of the reaction was investigated by DFT. The mechanism for ATH of the imines has been discussed on the basis of the DFT study.

Can silylenes rival transition metal systems in bond-strengthening pi-back donation? a computational investigation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2014)
Full quantum chemical calculations with density functional theory (DFT) show that bond-strengthening back-donation to a pi-diborene, recently discovered for transition metal systems (Braunschweig and co-workers, Nat. Chem., 2013, 5, 115-121), would be just as favored for Main Group silylene complexes. This result not only shows the range and applicability of the bond-strengthening back-bonding interaction, but also showcases the capacity of silylene complexes to do new chemistry, such as the cooperative activation of carbon monoxide and carbon dioxide.

Donor decomposition by lewis acids in Ziegler-Natta catalyst systems: a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Organometallics, 2014)
The development of new donors (Lewis bases, usually containing oxygen atoms) is one of the chief areas of research in Ziegler-Natta (ZN) olefin polymerization systems. The addition of such donors has led to improvement in the activity and selectivity of ZN systems. However, in order for the donor to be effective, it has to be chemically stable and resistant to decomposition by Lewis acidic species such as AlEt3. Discussed in the current work is the chemical stability of different ester donors, including aromatic benzoate donors and the silyl ester-a promising new donor class in ZN systems. Full quantum chemical calculations with density functional theory (DFT) indicate that esters can undergo decomposition through different pathways upon interaction with species such as the AlEt3 dimer: Al2Et6. Moreover, the studies show that the active, supported titanium catalyst species can cause donor decomposition and, in fact, is likely to be the greater threat to donor decomposition than Al2Et6. This explains why the addition of excess donors can lead to the poisoning of the active site in ZN systems. We have also computationally investigated means of improving the silyl ester donors in order to make them more robust and resilient to donor decomposition by Al2Et6 and the supported active titanium species.

Iodine-catalyzed aromatization of tetrahydrocarbazoles and its utility in the synthesis of glycozoline and murrayafoline A: a combined experimental and computational investigation - Humne, Vivek T.; Dangat, Yuvraj B.; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2014)
A new protocol for the aromatization of tetrahydrocarbazoles has been achieved using a catalytic amount of iodine, giving high yields. The role of iodine in the aromatization has been explained by DFT, and its wide scope is extended to the total synthesis of glycozoline and murrayafoline A. This method has proven to be tolerant of a broad range of functional groups.

Nature of the active site in ziegler-natta olefin polymerization catalysis systems - a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (European Journal of Inorganic Chemistry, 2014)
Pull quantum chemical calculations with density functional theory (DET) show that a principal role of donors in Ziegler-Nana (ZN) oh-din polymerization catalysts is to coordinate to the metal center at the active sites on the MgCl2 surface. Thereby, the behavior of the catalyst is modulated to favor insertion over termination and, thus, polymerization occurs. This is shown to be true for a range of different donors. The calculations indicate that active sites that feature anionic chloride ligands at the titanium center (the conventional model for the active site) would lead to lower-molecular-weight riolymers. If an -OC2H5 group were present instead of a chloride ligand, the active site would much more effectively produce long chain polymers. Therefore, the current work provides important new insights into the nature of the ZN polymerization process.
Keywords: Alkene polymerization; Density functional calculations; heterogeneous catalysis; Insertion; Polymers

New insights into small molecule activation by acyclic silylenes: a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2014)
Recently synthesized acyclic silylenes have the potential to rival transition metal complexes in performing single site small molecule activation, which is significant because of the need to find cheap and green alternatives to transition metal complexes for this important class of reactions. However, the current computational study, a full quantum chemical investigation with density functional theory, demonstrates that undesired side reactions would be competitive in these systems during small molecule activation. The current investigation, in addition to shedding light on this problem, also provides solutions on how the undesired side reactions during small molecule activation can be avoided.

Proposing efficient new pendant group polymer electrolyte membranes for fuel cells: a computational study - Mane, Manoj V.; Vanka, Kumar (Journal of Physical Chemistry C, 2014)
There is a need to develop new membranes for fuel cells that can conduct protons with high efficiency and at high temperatures. This paper reports a theoretical study of proton transfer barriers in newly proposed polymer electrolyte membranes (PEMs), having pendant nitrogen containing crown ether groups on an alkyl backbone. The proton transfer in the proposed pendant group PEMs would occur without the need of an external agent such as water or phosphoric acid, and without the need for the pendant groups to rotate and reorient themselves after each proton transfer. The current study shows that this would make the proposed PEMs very efficient, with low proton transfer barriers. This has been seen to be true for a range of different PEM cases considered, differing in the number of linker atoms in the alkyl backbone and in the number of nitrogens contained in each pendant group, thus, indicating the potential of the proposed structures as PEMs for fuel cells.

Synthesis of alpha,beta-unsaturated delta-lactones by vinyl acetate mediated asymmetric cross-aldol reaction of acetaldehyde: mechanistic insights - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali (European Journal of Organic Chemistry, 2014)
A tandem asymmetric cross-aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric beta-hydroxy aldehydes. By using this methodology we have accessed alpha,beta-unstaurated delta-lactones as well as isochromenones with high enantioselectivities from both asymmetric beta-hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross-aldol reaction of acetaldehyde and in the key cis/trans isomerisation step in the synthesis of d-lactones.
Keywords: Aldol reactions; asymmetric catalysis; lactones; reaction mechanisms

Can substituted allenes be highly efficient leaving groups in catalytic processes? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Journal of Computational Chemistry, 2015)
There is considerable interest presently in the chemistry of allenes. The current computational investigation looks into the possibility of using allenes and their derivatives as leaving groups. As it is well known, leaving groups are significant in catalytic processes for generating the active site. A full quantum mechanical study using density functional theory shows that allenes and their derivatives can function as excellent leaving groups. Indeed, the calculations show that they can be several orders of magnitude more effective than existing ligands for this purpose. The modification of second generation Grubbs' catalysts with these ligands suggests that the allene ligand cases that would be most effective are those having electron withdrawing groups, especially those that have the potential for supramolecular interactions between the substituent groups in the free state. (c) 2015 Wiley Periodicals, Inc.
Keywords: allenes; carbones; Density functional theory; olefin metathesis; supramolecular interactions

Computational study of metal free alcohol dehydrogenation employing frustrated lewis pairs - Mane, Manoj V.; Rizvi, Masood A.; Vanka, Kumar (Journal of Organic Chemistry, 2015)
The catalysis of acceptorless alcohol dehydrogenation (AAD) is an important area of research. Transition metal-based systems are known to be effective catalysts for this reaction, but developing metal free catalytic systems would lead to highly desirable cheaper and greener alternatives. With this in mind, this computational study investigates design strategies than can lead to metal free frustrated Lewis pairs (FLPs) that can be employed for AAD catalysis. A careful study of 36 different proposed FLP candidates reveals that several new FLPs can be designed from existing, experimentally synthesized FLPs that can rival or be even better than state-of-the-art transition metal-based systems in catalyzing the alcohol dehydrogenation process.

Gold(I)/chiral brønsted acid catalyzed enantioselective hydroamination-hydroarylation of alkynes: effect of remote hydroxyl group in the reactivity and enantioselectivity - Shinde, Valmik S.; Mane, Manoj V.; Vanka, Kumar; Mallick, Arijit; Patil, Nitin T. (Chemistry - A European Journal, 2015)

Mechanism of oxygen atom transfer from Fe-V(O) to olefins at room temperature - Singh, Kundan K.; Tiwari, Mrityunjay K.; Dhar, Basab B.; Vanka, Kumar; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
In biological oxidations, the intermediate Fe-V(0)(OH) has been proposed to be the active species for catalyzing the epoxidation of alkenes by nonheme iron complexes. However, no study has been reported yet that elucidates the mechanism of direct O-atom transfer during the reaction of Fe-V(0) with alkenes to form the corresponding epoxide. For the first time, we study the mechanism of O-atom transfer to alkenes using the Fe-V(0) complex of biuret-modified Fe-TAML at room temperature. The second-order rate constant (k(2)) for the reaction of different alkenes with Fe-V(0) was determined under single-turnover conditions. An 8000-fold rate difference was found between electron-rich (4-methoxystyrene; k(2) = 216 M-1 s(-1)) and electron-deficient (methyl transcinnamate; k(2) = 0.03 M-1 s(-1)) substrates. This rate difference indicates the electrophilic character of Fe-V(0). The use of cis-stilbene as a mechanistic probe leads to the formation of both cis- and trans-stilbene epoxides (73:27). This suggests the formation of a radical intermediate, which would allow C-C bond rotation to yield both stereoisomers of stilbene-epoxide. Additionally, a Hammett rho value of -0.56 was obtained for the para-substituted styrene derivatives. Detailed DFT calculations show that the reaction proceeds via a two-step process through a doublet spin surface. Finally, using biuret-modified Fe-TAML as the catalyst and NaOCl as the oxidant under catalytic conditions epoxide was formed with modest yields and turnover numbers.

Silica microspheres containing high density surface hydroxyl groups as efficient epoxidation catalysts - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Vanka, Kumar; Biradar, Ankush V. (RSC Advances, 2015)
Uniformly sized silica microspheres were synthesized by a hydrolysis-condensation method. The obtained material was etched with a mild aqueous potassium hydroxide solution for different periods of time to break their Si-O-Si bonds and increases the density of hydroxyl groups on their surfaces. The resulting materials were then used as transition metal-free catalysts for oxidation of olefins in the presence of hydrogen peroxide as a green oxidant. The materials were thoroughly characterized using various physicochemical techniques. These highly populated hydroxyl groups on the surface of silica microspheres were proven to be responsible for excellent conversion (up to 93%) and epoxide selectivity (up to 100%) for various olefins. Quantum mechanical calculations also corroborate the experimental findings. Furthermore, both experimental and theoretical studies show that tertiary silanols were present at the active sites of the catalyst surface and were responsible for olefin epoxidation.

Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Au(I)/Ag(I) co-operative catalysis: interception of Ag-bound carbocations with α-gold(I) enals in the imino-alkyne cyclizations with N-allenamides - Bagle, Pradip N.; Mane, Manoj V.; Vanka, Kumar; Shinde, Dinesh R.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2016)

Can main group systems act as superior catalysts for dihydrogen generation reactions? A computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2016)
The protolytic cleavage of the O-H bond in water and alcohols is a very important reaction, and an important method for producing dihydrogen. Full quantum chemical studies with density functional theory (DFT) reveal that germanium based complexes, such as HCCMeArB(2)GeH (Ar = 2,6-(Pr2C6H3)-Pr-i), with the assistance of silicon based compounds such as SiF3H, can perform significantly better than the existing state-of-the-art post-transition metal based systems for catalyzing dihydrogen generation from water and alcohols through the protolysis reaction.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

Effect of donors on the activation mechanism in ziegler-natta catalysis: a computational study - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Chemcatchem, 2016)
Full quantum chemical calculations, using density functional theory (DFT), have been conducted to explain the effect of donors on the ``activation mechanism'' in the Ziegler-Natta (Z-N) catalyst system. In the activation mechanism, the inactive (TiCl4)-Cl-IV catalyst converts into the active (TiCl2Et)-Cl-III catalyst with the help of the AlEt3 present in the system. The donors that have been considered in this study are: ethyl benzoate (eb), two representative diether cases, a phthalate donor, and a silyl ester donor. The results indicate that eb and the diether donor cases donor have a negative effect on the barriers for the activation mechanism. However, the eb donor can be displaced from the MgCl2 surface by AlEt3, which matches experimental observations. For the phthalate, silyl ester and TiCl3-OC4H8Cl cases, the results indicate that a significant induction period would be present in Z-N systems employing such donors or having such a catalytic center, before catalysis could commence.
Keywords: Alkylation; aluminum; Density functional calculations; surface chemistry; titanium

Exploration of the diastereoselectivity in an unusual Grignard reaction and its application towards the synthesis of styryl lactones 7-epi-(+)-goniodiol and 8-epi-(-)-goniodiol - Chavan, Subhash P.; Khatod, Harshali S.; Das, Tamal; Vanka, Kumar (RSC Advances, 2016)
An unusual diastereoselective Grignard reaction is explored, where the Grignard reagents are derived from 1,n-dihaloalkanes. A steric bias due to the presence of a quaternary centre adjacent to the acetonide ester at the benzylic position is responsible for the formation of an intramolecularly reduced product in almost quantitative yield. This steric hindrance is responsible for the diastereoselectivity observed with a variety of aromatic as well as aliphatic esters. The unusual Grignard reaction furnishes long chain secondary alcohols possessing a terminal olefin, which are synthetically important intermediates. As an application of this method, the diastereoselective synthesis of styryl lactones viz. 7-epi-(+)-goniodiol (29) and 8-epi(-)-goniodiol (30) has been achieved.

Exploring activity differences between the hydroformylation catalysts: Insights from theory - Dangat, Yuvraj B.; Rizvi, Masood Ahmad; Pandey, Pippalad; Vanka, Kumar (Journal of Organometallic Chemistry, 2016)
Hydroformylation catalysis is the most important homogeneous catalysis process of the current day. The current computational investigation aims to understand the nature of the hydroformylation process when monodentate ligands are employed. The complete catalytic cycle for different monodentate ligands bound to the rhodium center has been studied with full quantum chemical calculations, with density functional theory (DFT). To the best of our knowledge, this is the first systematic investigation of the relative free energy surfaces for mono-coordinate monodentate and bi-coordinated monodentate ligands in hydroformylation catalysis. The results indicate that the barriers are lower for the mono-coordinate monodentate species in comparison to the bi-coordinate monodentate, for all the ligand cases studied, indicating higher activity for the mono-coordinate monodentate active species. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Density functional theory (DFT) calculations; Hydroformylation; Monodentate; Rhodium

Exploring the reducing role of boron: added insights from theory - Dangat, Yuvraj B.; Vanka, Kumar (Dalton Transactions, 2016)
Carbon-carbon coupling in CO molecules is a challenging proposition, and very few main group complexes have been shown to effect this process. A recently reported triply bonded diboryne system (1) is notable for coupling four CO molecules to produce a (bis) boralactone species. The current full quantum chemical computational investigation with density functional theory (DFT) provides important insights into the nature of the CO coupling process by triply bonded diboryne systems. The complete reaction pathway leading to the formation of the (bis) boralactone has been determined. Factors that make this system so successful in coupling CO groups have been elucidated, and pertinent issues, such as why the coupling process stops after four CO additions, have been explored. Also, importantly, insights have been gained through the natural bond orbital (NBO) analysis into how the back-donation from diboryne activates CO.

Facile access to a Ge(II) dication stabilized by isocyanides - Swamy, V. S. V. S. N.; Yadav, Sandeep; Pal, Shiv; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2016)
Herein, we introduce isocyanide as a ligand in main group chemistry and describe the facile isolation of a Ge(II) dication. The reaction of 2,6-dimethylphenylisocyanide with GeCl2 leads to the formation of a Ge(II) dication with two [GeCl3](-) molecules as counter anions. The dicationic Ge(II) center is bound to four isocyanide ligands and also holds a lone pair of electrons. DFT calculations reveal that the dication is stabilized only by sigma-donation from the four isocyanide ligands. Natural population analysis gives a charge of +0.74 on the Ge(II) center, indicating that the positive charge is shared by the isocyanide substituents.

Intramolecular dehydrogenative coupling of 2,3-diaryl acrylic compounds: access to substituted phenanthrenes - Gupta, Vijay; Rao, V. U. Bhaskara; Das, Tamal; Vanka, Kumar; Singh, Ravi P. (Journal of Organic Chemistry, 2016)
A simple, facile, and environmentally benign intramolecular dehydrogenative coupling of various 1,2-diarylethylenes for the synthesis of phenanthrenes in excellent yield has been described. This new methodology uses ceric ammonium nitrate (CAN) as a promoter at room temperature and has been extended to intermolecular synthesis of biaryl compounds. The electron transfer from methoxyarene to cerium leads to cationic radical formation, which further proceeds to intramolecular coupling. Preliminary mechanistic investigation by EPR spectroscopy and density functional theory calculation suggested a similar view.

Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.

Reductive nitrosylation of nickel(II) complex by nitric oxide followed by nitrous oxide release - Ghosh, Somnath; Deka, Hemanta; Dangat, Yuvraj B.; Saha, Soumen; Gogoi, Kuldeep; Vanka, Kumar; Mondal, Biplab (Dalton Transactions, 2016)
Ni(II) complex of ligand L (L = bis(2-ethyl-4-methylimidazol-5-yl)methane) in methanol solution reacts with an equivalent amount of NO resulting in a corresponding Ni(I) complex. Adding further NO equivalent affords a Ni(I)-nitrosyl intermediate with the NiNO(10) configuration. This nitrosyl intermediate upon subsequent reaction with additional NO results in the release of N2O and formation of a Ni(II)-nitrito complex. Crystallographic characterization of the nitrito complex revealed a symmetric eta(2)-O,O-nitrito bonding to the metal ion. This study demonstrates the reductive nitrosylation of a Ni(II) center followed by N2O release in the presence of excess NO.

Small molecule activation by constrained phosphorus compounds: insights from theory - Pal, Amrita; Vanka, Kumar (Inorganic Chemistry, 2016)
An exciting new development in main group chemistry has been the use of a constrained, flat, phosphorus-based complex to mediate in reactions such as the dehydrogenation of ammonia borane (AB), and the activation of the NH bond in primary amines. Its importance is based on the fact that it shows that main group compounds, when properly designed, can be as effective as transition metal complexes for doing significant chemical transformations. What the current computational study, employing density functional theory (DFT), reveals is that a common, general mechanism exists that accounts for the behavior of the flat phosphorus compound in the different reactions that have been experimentally reported to date. This mechanism, which involves the mediation by a base as a proton transfer agent, is simpler and energetically more favorable than the previous mechanisms that have been proposed for the same reactions in the literature. It is likely that the knowledge gained from the current work about the chemical behavior of this phosphorus compound can be utilized to design new constrained phosphorus-based compounds.

Unraveling origins of the heterogeneous curvature dependence of polypeptide interactions with carbon nanostructures - Jana, Asis K.; Tiwari, Mrityunjay K.; Vanka, Kumar; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2016)
Emerging nanotechnology has rapidly broadened interfacial prospects of biological molecules with carbon nanomaterials (CNs). A prerequisite for effectively harnessing such hybrid materials is a multifaceted understanding of their complex interfacial interactions as functions of the physico-chemical characteristics and the surface topography of the individual components. In this article, we address the origins of the curvature dependence of polypeptide adsorption on CN surfaces (CNSs), a phenomenon bearing an acute influence upon the behavior and activity of CN-protein conjugates. Our benchmark molecular dynamics (MD) simulations with the amphiphilic full-length amyloid beta (A beta) peptide demonstrate that protein adsorption is strongest on the concave (inner) CN-surface, weakest on the convex (outer) surface, and intermediary on the planar surface, in agreement with recent experimental reports. The curvature effects, however, are found to manifest non-uniformly between the amino acid subtypes. To understand the underlying interplay of the chemical nature of the amino acids and surface topography of the CNs, we performed high-level quantum chemical (QM) calculations with amino acid analogs (MA) representing their five prominent classes, and convex, concave and planar CN fragments. Molecular electrostatic potential maps reveal pronounced curvature dependence in the mixing of electron densities, and a resulting variance in the stabilization of the non-covalentty bound molecular complexes. Interestingly, our study revealed that the interaction trends of the high-level QM calculations were captured well by the empirical force field. The findings in this study have important bearing upon the design of carbon based bio-nanomaterials, and additionally, provide valuable insights into the accuracy of various computational techniques for probing non-bonded interfacial interactions.

DBU-mediated diastereoselective aldol-type cyanomethylation of isatins - Rao, V. U. Bhaskara; Kumar, Krishna; Das, Tamal; Vanka, Kumar (Journal of Organic Chemistry, 2017)
An efficient, metal-free approach to 3-substituted 3-hydroxybxindole by DBU-mediated highly diastereoselective addition of aryl acetonitrile to N-protected isatin under mild conditions has been developed. The reaction proceeds smoothly to produce respective cyanomethylated adducts in good yield and excellent diastereoselectivity. Further transformation of the cyanide group allowed the synthesis of an advance intermediate of corresponding (+/-) CPC analogue. The mechanistic insight :toward the aldol-type cyanomethylation, of N-tritylisatin with benzyl cyanide was obtained by DFT calculations.

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Exploiting directional long range secondary forces for regulating electrostatics dominated noncovalent interactions - Tiwari, Mrityunjay; Vanka, Kumar (Chemical Science, 2017)
It has been well established that long range secondary electrostatic interactions (SEIs) have a significant effect on the stability of supramolecular complexes. However, general rules for exploiting SEIs in the rational design of diverse supramolecular complexes have been difficult to obtain. In this work, we outline a quantum chemical approach for understanding the strength of electrostatic interactions. This approach is seen to provide excellent correlation between the electrostatic force and the binding energy between two partners in hydrogen-bonded complexes, as well as that between two ions in ion-pair complexes. Furthermore, we illustrate how the understanding of the binding allows for the rational design of new complexes where the association constant between the two partners can be increased or decreased, as desired, by several orders of magnitude. Hence, the current work showcases a general, simple and powerful method of understanding and exploiting long range secondary electrostatic interactions.

Interplaying anions in a supramolecular metallohydrogel to form metal organic frameworks - Karak, Suvendu; Kumar, Sushil; Bera, Saibal; Diaz Diaz, David; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
The remarkable effect of anions on the transition from supramolecular gels to crystalline phases has been described. An amino acid-based metallohydrogel was transformed into different metal-organic frameworks through the selective picking of anions. The metallohydrogel and the resulting metal-organic frameworks (MOFs) were thoroughly characterized. The results demonstrated controlled access over the binding of a particular anion to selectively form a particular MOF.

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Molecular motifs for additives that retard PEO crystallization - Shrivastava, Sudhakar Dinesh; Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Vanka, Kumar; Kumaraswamy, Guruswamy (Polymer Engineering & Science, 2017)
We investigate the influence of several bifunctional phenol additives (resorcinol: RES, hydroquinone: HYD, p-hydroxybenzoic acid: PHBA, and p-nitrophenol: PNP) on the crystallization of matrix polymer, polyethyleneoxide. We employ solid state Nuclear Magnetic Resonance spectroscopy (NMR), Differential Scanning Calorimetry (DSC), optical microscopy, and Small Angle X-ray Scattering (SAXS) to investigate crystallization of the additivated PEO and compare with Density Functional Theory (DFT) calculations of additive-PEO interactions. Additive-polymer interactions are a function of the functional groups on the additive. Temperature-dependent spherulitic growth rate measurements from optical microscopy and SAXS lamellar long spacings indicate a distinct trend in the effect of additives on PEO crystallization. Change in PEO crystallization is most pronounced with PNP, followed by PHBA and finally RES and HYD. This trend correlates qualitatively with the binding energies of additive-PEO interactions from DFT studies. Our results suggest that DFT calculations might be a useful screening tool to evaluate the influence of additives on polymer crystallization. POLYM. ENG. SCI., 2016. © 2016 Society of Plastics Engineers

Porous porphyrin organic polymer (PPOP) for visible light triggered hydrogen production - Mukherjee, Gargi; Thote, Jayshri; Aiyappa, Harshitha Barike; Kandambeth, Sharath; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
A visible light active porphyrin-based porous organic polymer having high chemical stability and surface area has been synthesized and its ability to influence the photocatalytic activity of large band gap-TiO2 nanoparticles has been tested. The resultant composite shows improved photocatalytic activity as compared to the parent precursors. This study provides insights into the photosensitizing ability of the polymer in addition to its ability to firmly harbor nanoparticles onto its surface.

p-Selective (sp(2))-C-H functionalization for an acylation/alkylation reaction using organic photoredox catalysis - Pandey, Ganesh; Tiwari, Sandip Kumar; Singh, Bhawana; Vanka, Kumar; Jain, Shailja (Chemical Communications, 2017)
p-Selective (sp(2))-C-H functionalization of electron rich arenes has been achieved for acylation and alkylation reactions, respectively, with acyl/alkylselenides by organic photoredox catalysis involving an interesting mechanistic pathway.

Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Unusual role of the aromatic solvent in single site Al(I) chemistry: insights from theory - Jain, Shailja; Vanka, Kumar (Chemistry - A European Journal, 2017)
The single site activation of strong σ bonds (such as that of H-H, P-H and N-H) remains a significant challenge in main group chemistry, with only a few cases reported to date. In this regard, recent exciting experiments done with Al(I) complexes hold significance, because they, too, have been seen to activate a variety of strong σ bonds. Such chemistry is generally seen to occur in aromatic solvents. The current computational studies with density functional theory (DFT) reveal the interesting reason for this: it is seen that an explicit aromatic solvent molecule acts as a catalyst by converting the Al(I) complex to Al(III) during the process. Different cases of σ bond activation by Al(I) complexes have been investigated and the efficiency for the H-X (X=H, NHtBu, PPh2) bond activation in the presence of an explicit benzene solvent molecule has been seen to be orders of magnitude higher than in its absence. The current work therefore reveals the chemistry of Al(I) complexes to be richer and more complex than realized to date, and shows it to be dependent on metal-solvent cooperativity, the first known example of its kind in main group chemistry.

Access to silicon(II)- and germanium(II)-indium compounds - Pahar, Sanjukta; Karak, Suvendu; Pait, Moumita; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2018)
Despite the remarkable ability of N-heterocyclic silylene to act as a Lewis base and form stable Lewis adducts with group 13 elements such as boron, aluminum, and gallium, there has been no such comparable investigation with indium and the realization of a stable silylene-indium complex has still remained elusive. Similarly, a germylene-indium complex is also presently unknown. We describe herein the reactions of [PhC(NtBu)(2)SiN-(SiMe3)(2)] (1) and [PhC(NtBu)(2)GeN(SiMe3)(2)] (4) with InCl3 and InBr3 that have resulted in the first silylene-indium complexes, [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InCl3] (2) and [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InBr3] (3), as well as the first germylene-indium complexes, [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InCl3] (5) and [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InBr3] (6). The solid-state structures of all species have been validated by single-crystal X-ray diffraction studies. Note that 5 and 6 are the first structurally characterized organometallic compounds that feature a Ge-In single bond (apart from the compounds in Zintl phases). Theoretical calculations reveal that the Si(II)-> In bonds in 2 and 3 and the Ge(II)-> In bonds in 5 and 6 are dative bonds.

B(C6F5)(3): catalyst or initiator? insights from computational studies into surrogate silicon chemistry - Banerjee, Subhrashis; Vanka, Kumar (ACS Catalysis, 2018)
One of the most promising recent developments in catalysis has been the use of the metal-free Lewis acid B(C6F5)(3) as a catalyst for a range of different chemical transformations. Perhaps the most impressive achievement in this regard is the recently accomplished in situ generation of SiH4 from surrogates (Simonneau and Oestreich, Nat. Chem., 2015,7, 816). However, what the current computational work, with density functional theory, reveals is that this process, in addition to being catalyzed by B(C6F5)(3), is also significantly dominated by a series of autocatalytic reactions. The results are further corroborated by the use of the energetic span model, which shows that the turnover frequency is higher for the newly proposed autocatalytic pathway in comparison to the conventional B(C6F5)(3)-catalyzed pathway. The current work therefore provides interesting new insights into surrogate silicon chemistry. But, more importantly, the current studies indicate that B(C6F5)(3) is likely to function more as an initiator rather than a pure catalyst in many metal-free transformations that have been reported to date.
Keywords: autocatalysis; Density functional theory; ion-pair; Lewis acid catalysis; reaction mechanism; surrogate silicone chemistry; tris(pentafluorophenyl)borane

Beyond hydrofunctionalisation: a well-defined calcium compound catalysed mild and efficient carbonyl cyanosilylation - Yadav, Sandeep; Dixit, Ruchi; Vanka, Kumar; Sen, Sakya S. (Chemistry-A European Journal, 2018)
Organocalcium compounds have been reported as efficient catalysts for various transformations, for cases in which one of the substrates contained an E-H (E=B, N, Si, P) bond. Here, we look at the possibility of employing an organocalcium compound for a transformation in which none of the precursors has a polar E-H bond. This study demonstrates the utilization of a well-defined amidinatocalcium iodide, [PhC(NiPr)(2)CaI] (1) for cyanosilylation of a variety of aldehydes and ketones with Me3SiCN under ambient conditions without the need of any co-catalyst. The reaction mechanism involves a weak adduct formation between 1 and Me3SiCN leading to the activation of the Si-C bond, which subsequently undergoes sigma-bond metathesis with a C=O moiety. Such a mechanistic pathway is unprecedented in alkaline earth metal chemistry. Experimental and computational studies support the mechanism.
Keywords: Ca catalysis; carbonyls; cyanosilylation; Density functional calculations; transition-metal free

Easily accessible lithium compound catalyzed mild and facile hydroboration and cyanosilylation of aldehydes and ketones - Bisai, Milan; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2018)
Simple and readily accessible lithium compounds such as 2,6-ditertbutyl phenolate lithium (1a), 1,1' dilithioferrocene (1b) and nacnac lithium (1c) are found to be efficient single site catalysts for hydroboration of...

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.

Mechanism of nickel(II)-catalyzed C(2)-H alkynylation of indoles with alkynyl bromide - Khake, Shrikant M.; Jain, Shailja; Patel, Ulhas N.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The nickel system (THF)(2)NiBr2/phen has recently been shown as an efficient catalyst for the C-H bond alkynylation of diverse heteroarenes with (triisopropylsilyl)alkynyl bromide via monodentate chelation assistance. Herein, we report an extensive mechanistic investigation for the direct alkynylation of indoles involving the well-defined nickel catalyst, which features a coordinative insertion pathway of alkynyl bromide with the Ni(II) catalyst. Catalytic relevant nickel complexes, (phen)NiCl2 (5), (phen)(2)NiCl2 (6) and [(phen)(3)Ni].NiCl4 (7) were isolated, and the complexes 6 and 7 were structurally characterized. Well-defined complexes were as competent as the in situ generated catalyst system (THF)(2)NiBr2/phen for the alkynylation of indoles. Various controlled studies and reactivity experiments were performed to understand the probable pathway for the alkynylation reaction. Kinetics analysis highlights that the complex (phen)NiX2 acts as a precatalyst, and the involvement of substrate indole and LiO'Bu are essential for the generation of the active catalyst. Deuterium labeling and kinetic studies suggest that the process involving C-H cleavage and carbo-nickelation of indole is a crucial rate influencing step. Reactivity study of various alkynyl compounds with nickel-species highlights a migratory insertion route for the reaction. DFT calculations firmly support the experimental findings and suggest the coordinative insertion pathway of alkynyl bromide rather than oxidative addition toward the nickel(II) center.

Mechanistic aspects of pincer nickel(II)-catalyzed C-H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Jain, Shailja; Pandey, Dilip K.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The quinolinyl-based pincer nickel complex, kappa(N),kappa(N),kappa(N)-{C9H6N-(mu-N)-C6H4-NMe2}NiCl [((NNNMe2)-N-Q)-NiCl; (1)] has recently been demonstrated to be an efficient and robust catalyst for the alkylation of azoles with alkyl halides under copper-free conditions. Herein, we report the detailed mechanistic investigation for the alkylation of azoles catalyzed by ((NNNMe2)-N-Q)NiCl (1), which highlights an iodine atom transfer (IAT) mechanism for the reaction involving a Ni-II/Ni-III process. Deuterium labeling experiments indicate reversible cleavage of the benzothiazole C-H bond, and kinetic studies underline a fractional negative rate order with the substrate benzothiazole. The involvement of an alkyl radical during the alkylation is validated by radical clock and external additive experiments. An active intermediate species ((NNNMe2)-N-Q)Ni(benzothiazolyl) (5a) has been isolated and structurally characterized. The complex ((NNNMe2)-N-Q)Ni(benzothiazoly1) (5a) is found to be the resting state of catalyst 1. Kinetic analysis of electronically different intermediates suggests that the step involving the reaction of 5a with alkyl iodide is crucial and a rate-influencing step. DFT calculations strongly support the experimental findings and corroborate an IAT process for the alkylation reaction.

Mechano-responsive room temperature luminescence variations of boron conjugated pyrene in air - Wakchaure, Vivek C.; Ranjeesh, Kayaramkodath C.; Goudappagouda; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh; Babu, Sukumaran S. (Chemical Communications, 2018)
Stimuli responsive tunable luminescence is a promising field of research. Even though mechanofluorescence is widely studied, mechanophosphorescence remains unexplored. Here we report the mechano-driven fluorescence and phosphorescence variations of a pyrene tetraboronic ester derivative. The fluorochromic and room temperature phosphorescence features are supported by theoretical studies and single crystal analysis. The mechanically ground fluorescence active but phosphorescence inactive pyrene tetraboronic ester exhibits room temperature phosphorescence in air withmechanical force. The efficient intermolecular electronic coupling in the dimer formed upon scratching enables a good communication between singlet and triplet states, hence resulting in room temperature mechanophosphorescence.

Role of the (104) MgCl2 lateral cut in ziegler-natta catalysis: a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2018)
Density functional theory (DFT) has been used for the study of ethylene polymerization in the Ziegler-Natta (ZN) olefin polymerization system for eight different alkoxy group containing titanium catalysts (Cat-A-h), Ti(III)Et(OR)(OR') (where R =-CH3,-Et,-tert-butyl, cyclohexane, R' = CH3,-Et,-tert-butyl, cyclohexane). What is of significance is that the catalysts studied were all considered to be tethered to the (104) MgCl2 surface, which has traditionally been considered a ``dormant'' surface in Z-N catalysis systems, in contrast to the ``more active'' (110) MgCl2 surface. Our calculations indicate that the binding of all the catalysts to the (104) surface is favorable, even after taking entropic effects into account. For purposes of comparison, ethylene polymerization has been investigated for the Cat-C (TiEt(OEt)(2)) and the Cat-H (TiEt(CI)(OC4H8Cl)) (OC4H8Cl = the chlorobutoxy group) cases, for both the (i) (110) and the (ii) (104) MgCl2 surfaces. It has been seen that for both (i) and (ii)-the energy gap between insertion and the termination barriers (Delta X) was nearly the same for both the Cat-C and Cat-H eases, which shows that ethylene polymerization on the (104)MgCl2 surface is likely to be a ptoininent occurrence in Z-N catalysis, when alkoxy groups are bound to the titanium center. Additionally, for the Cat-C and the Cat-H cases, the regio-and stereoselective behavior of the propylene monomer on the titanium species present on the (110) and the (104) MgCl2 surfaces has also been investigated, and the results indicate that the (104) MgCl2 surface is only slightly less effective than the (110. However, the calculations also indicate that for Cat-H the (104) MgCl2 surface significantly improves the molecular weight of polypropylene in comparison to the (110) surface, further showcasing how the (104) surface (ignored until date) might be a major player in ZN catalysis. Given that a major portion of the MgCl2 support is made up of (104) lateral cuts, the current findings are of considerable relevance.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Understanding interactions between lignin and ionic liquids with experimental and theoretical studies during catalytic depolymerisation - Singh, Sandip Kumar; Banerjee, Subhrashis; Vanka, Kumar; Dhepe, Paresh Laxmikant (Catalysis Today, 2018)
Compared to H2SO4, Bronsted acidic ionic liquid (BAIL, [C3SO3HMIM][HSO4]) catalyzed depolymerization of lignin yielded higher concentration of low molecular weight products under mild conditions (120 degrees C) as proven by GC and GC-MS. To comprehend this disparity in catalytic activity among H2SO4 and BAIL (at similar H+ concentration), experimental techniques [1D(H-1) NMR, 2D(N-15/H-1 HMBC) NMR and RAMAN] have been employed. Based on these studies, it has been proven that the transfer of electron density from substrate to the electron deficient imidazolium ring via formation of hydrogen bond between -OH/OCH3 (substrate) and -N1C2H2N3-(cation) is possible, while the anion plays an important role. Further, density functional theory (DFT) calculations also corroborated this fact by showing a change in the bond angle and decrease in bond length (C-2-H-2 in imidazole), due to the presence of weak and strong hydrogen bonding between the substrate and IL.

Can the solvent enhance the rate of chemical reactions through C-H/pi interactions? insights from theory - Jain, Shailja; Vanka, Kumar (Physical Chemistry Chemical Physics, 2019)
The current computational study with density functional theory (DFT) shows that the rate of chemical reactions can be influenced through non-covalent C-H/p interactions between substrates and the solvent. It is shown that intramolecular carbon-carbon interaction and CO2 activation by a low valent silicon complex are both favourably affected by the explicit presence of the solvent toluene, due to C-H/p interactions between toluene and the silicon complex. Furthermore, ab initio molecular dynamics (AIMD) simulations demonstrate that even if the C-H/p interacting solvent molecule is displaced from the complex, another would quickly take its place, thus maintaining the interaction. Hence, the current work shows how non-covalent interactions between solvent and substrate can enhance the rate of the reaction and expands our understanding of the role and influence of the solvent in effecting important chemical transformations.

Diastereoselective multi-component tandem condensation: synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles - Gupta, Vijay; Sahu, Debashish; Jain, Shailja; Vanka, Kumar; Singh, Ravi P. (Organic & Biomolecular Chemistry, 2019)
A general strategy for a one-pot stereoselective synthesis of 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles by reaction of salicylaldehyde, malononitrile and butenolides via a tandem Knoevenagel/Pinner/vinylogous Michael condensation is presented. The beta,gamma-butenolides gave a syn-selective MCR adduct with a dr up to 11.5 : 1. The mechanistic insight into the MCR was obtained by DFT calculations.

Insights into the origin of life: did it begin from HCN and H2O? - Das, Tamal; Ghule, Siddharth; Vanka, Kumar (Acs Central Science, 2019)
The seminal Urey-Miller experiments showed that molecules crucial to life such as HCN could have formed in the reducing atmosphere of the Hadean Earth and then dissolved in the oceans. Subsequent proponents of the "RNA World" hypothesis have shown aqueous HCN to be the starting point for the formation of the precursors of RNA and proteins. However, the conditions of early Earth suggest that aqueous HCN would have had to react under a significant number of constraints. Therefore, given the limiting conditions, could RNA and protein precursors still have formed from aqueous HCN? If so, what mechanistic routes would have been followed? The current computational study, with the aid of the ab initio nanoreactor (AINR), a powerful new tool in computational chemistry, addresses these crucial questions. Gratifyingly, not only do the results from the AINR approach show that aqueous HCN could indeed have been the source of RNA and protein precursors, but they also indicate that just the interaction of HCN with water would have sufficed to begin a series of reactions leading to the precursors. The current work therefore provides important missing links in the story of prebiotic chemistry and charts the road from aqueous HCN to the precursors of RNA and proteins.

Lithium compounds as single site catalysts for hydroboration of alkenes and alkynes - Bisai, Milan Kumar; Yadav, Sandeep; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2019)
The hydroboration of alkenes and alkynes using easily accessible lithium compounds [2,6-di-tert-butyl phenolatelithium (1a) and 1,1 ` dilithioferrocene (1b)] has been achieved with good yields, high functional group tolerance and excellent chemoselectivity. Deuterium-labeling experiments confirm the cis-addition of pinacolborane. The methodology has been further extended to myrcene, which undergoes selective 4,3-hydroboration. DFT calculations provide insights into the mechanism.

Metal-free regioselective cross dehydrogenative coupling of cyclic ethers and aryl carbonyls - Mane, Kishor D.; Mukherjee, Anagh; Vanka, Kumar; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2019)
A highly regioselective, efficient, and metal-free oxidative cross dehydrogenative coupling (CDC) of aryl carbonyls with cyclic ethers has been developed. This method offers easy access to substituted alpha-arylated cyclic ethers with a high functional group tolerance in good to excellent yields. The regioselectivity of this CDC reaction was confirmed by density functional theory (DFT)-based calculations.

Silylene induced cooperative B-H bond activation and unprecedented aldehyde C-H bond splitting with amidinate ring expansion - Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S.; Roesky, Herbert W. (Chemical Communications, 2019)
The addition of HBpin to PhC(NtBu)(2)SiN(SiMe3)(2) (1) results in the cleavage of the B-H bond in a cooperative fashion across the Si and amidinate-C sites. The reaction of 1 with benzaldehyde led to C-H bond activation with amidinate ring expansion leading to a five-membered heterocycle. In case of 4-fluorobenzaldehyde, a C-C bond coupling takes place leading to a dioxasilolane derivative as the major product.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

Access to diverse germylenes and a six-membered dialane with a flexible beta-diketiminate - Pahar, Sanjukta; Swamy, V. S. V. S. N.; Das, Tamal; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2020)
A nacnac-based tridentate ligand containing a picolyl group (L) was employed to isolate chlorogermylene (1). The reaction of1with another equivalent of GeCl2 center dot dioxane surprisingly gave pyridylpyrrolide-based chlorogermylene (2)viaC-N bond cleavage and C-C coupling, while with AlCl3, it afforded a transmetalated product,4. The reaction of L with AlH3 center dot NMe2Et led to an unusual cyclohexane type six-membered dialane heterocycle (5).

Amidinato germylene-zinc complexes: synthesis, bonding, and reactivity - Yadav, Sandeep; Kumar, Rohit; Raj, K. Vipin; Yadav, Prashant; Vanka, Kumar; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
Despite the explosive growth of germylene compounds as ligands in transition metal complexes, there is a modicum of precedence for the germylene zinc complexes. In this work, the synthesis and characterization of new germylene zinc complexes [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> ZnX2](2)(X= Br (2) and I (3)) supported by (benz)-amidinato germylene ligands are reported. The solid-state structures of2and3have been validated by single-crystal X-ray diffraction studies, which revealed the dimeric nature of the complexes, with distorted tetrahedral geometries around the Ge and Zn center. DFT calculations reveal that the Ge-Zn bonds in2and3are dative in nature. The reaction of2with elemental sulfur resulted in the first structurally characterized germathione stabilized ZnBr(2)complexes PhC(NtBu)(2)Ge(=S){N(SiMe3)(2)}-> ZnBr2(5). Therefore, the Ge=S in5is in-between Ge-S single and Ge=S double bond length, owing to the coordination of a sulfur lone pair of electrons to ZnBr2.
Keywords: DFT; Germathione; Germylene; X-ray Structure; zinc

Catalytic reductive deoxygenation of esters to ethers driven by hydrosilane activation through non-covalent interactions with a fluorinated borate salt - Rysak, Vincent; Dixit, Ruchi; Trivelli, Xavier; Merle, Nicolas; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysis Science & Technology, 2020)
We report the catalytic and transition metal-free reductive deoxygenation of esters to ethers through the use of a hydrosilane and a fluorinated borate BArF salt as a catalyst. Experimental and theoretical studies support the role of noncovalent interactions between the fluorinated catalyst, the hydrosilane and the ester substrate in the reaction mechanism.

Effect of solvent-substrate noncovalent interactions on the diastereoselectivity in the intramolecular carbonyl-ene and the staudinger [2+2] cycloaddition reactions - Jain, Shailja; Vanka, Kumar (Journal of Physical Chemistry A, 2020)
Noncovalent interactions (NCIs) have been identified as important contributing factors for determining selectivity in organic transformations. However, cases where NCIs between solvents and substrates are responsible for a major extent for determining selectivity are rare. The current computational study with density functional theory identifies two important transformations where this is the case: the intramolecular carbonyl-ene reaction and the Staudinger [2 + 2] cycloaddition reaction. In both cases, the role of explicit solvent molecules interacting non-covalently with the substrate has been taken into account. Calculations indicate that the diastereomeric ratio would be 95.0:5.0 for the formation of tricyclic tetrahydrofuran diastereomers via the intramolecular carbonyl-ene reaction and 94.0:6.0 for the formation of the triflone diastereomers via the Staudinger [2 + 2] cycloaddition reaction, which corroborates with the experiment. Interestingly, in both the cases, the calculations indicate that noninclusion of explicit solvent molecules would lead to only a small difference between the competing transition states, which leads to the conclusion that solvent-substrate NCIs are the major cause for diastereoselectivity in both the cases considered.

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

Highly efficient chemoselective N-tert butoxycarbonylation of aliphatic/aromatic/heterocyclic amines using diphenylglycoluril as organocatalyst - Awasthi, Amardeep; Mukherjee, Anagh; Singh, Mandeep; Rathee, Garima; Vanka, Kumar; Chandra, Ramesh (Tetrahedron, 2020)
An efficient approach for the Chemoselective N-tert-butoxycarbonylation of a variety of amines using diphenylglycoluril as organocatalyst has been described. For the first time, a plausible mechanism for the N-tert-butoxycarbonylation has been proposed using density functional theory (DFT) calculations supported by NMR studies. The reusability of the organocatalyst and observation of the desired N-Boc protected amines being formed without the formation of side products like urea, oxazolidinone, isocyanate, and N, N-di-Boc derivatives makes the present protocol desirable. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: DFT studies; Diphenylglycouril; N-tert butoxycarbonylation; organocatalyst; Proton shuttle mechanism

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Transmetallation vs adduct: diverse reactivity of N,O-ketiminato germylene with [Cp*MCl2](2) (M = Rh or Ir; Cp* = eta(5)-C5Me5) and MCl5 (M = Nb and Ta) - Raghavendra, Beesam; Bakthavachalam, K.; Das, Tamal; Roisnel, Thierry; Sen, Sakya S.; Vanka, Kumar; Ghosh, Sundargopal (Journal of Organometallic Chemistry, 2020)
The reactions of the germylenes, [(Dipp)NCMeCHCORGeCl] (1a: R = Me, 1b: R = Ph) with [Ir2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] led to the formation of the adducts [(Dipp)NCMeCHCORGeClIrCl2Cp*] (3a: R = Me and 3b: R = Ph). On the other hand, [Rh2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] does not react with the germylenes (1a and 1b). When the reactions of 1a and 1b are carried out with [Cp*TaCl4], the reaction led to decomposition. The reaction of 1a or 1b with TaCl5 yielded the transmetallated products [(Dipp)NCMeCHCORTaCl4] (4a: R = Me, 4b: R = Ph) with the extrusion of GeCl2. Our theoretical studies show that for, the insertion of TaCl5 to 1a and the formation of 4a with concomitant elimination of GeCl2 is energetically favourable. Extrusion of SnCl2 is also observed when the corresponding stannylene, [(Dipp)NCMeCHCOMeSnCl] was reacted with TaCl5. All these compounds have been characterized by H-1 and C-13 NMR spectroscopy, elemental analysis and the constitution of compounds 1b, 3b, and 4a were confirmed by single-crystal X-ray crystallography. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Adduct formation; Germylenes; Iridium; Ketoiminate; Tantalum; Transmetallation

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium

Unraveling the hidden role of the counteranion in ``cation in a cage'' systems - Mukherjee, Anagh; Ghule, Siddharth; Tiwari, Mrityunjay K.; Vanka, Kumar (Journal of Physical Chemistry A, 2020)
The current work showcases general principles at play in systems consisting of cations present inside molecular cages. Such systems, relevant to chemistry and biology, have been carefully investigated by computational methods. The important Ge(II)-encapsulating cage systems have been studied first. The very fact that such compounds exist appears highly unlikely, given the highly reactive nature of the Ge(II) dication. Our studies reveal what really occurs in solution when such complexes are formed: the Ge(II) dications are actually present as [Ge-X](+) (where X is the ``non-coordinating'' counterion employed in such systems) during entry and subsequent existence at the center of the cage. Hence, what is actually present is a ``pseudomonocation''. Interestingly, such pseudomonocation-encapsulated cages are seen to be equally relevant in systems of biological importance, such as for dicationic s block-based ionophores. In explaining such cases, the concept of ``isoionicity'' is introduced, demonstrating that the counterion-coordinated dications are isoionic with a monocation, such as Li(I), isolated in the same ionophore.

Vinylogous michael addition of 3-alkylidene-2-oxindoles to beta,gamma-unsaturated alpha-keto esters by bifunctional cinchona alkaloids - Jaiswal, Manish K.; Kumar, Rajesh; Singh, Sanjay; Jain, Shailija; Vanka, Kumar; Singh, Ravi P. (European Journal of Organic Chemistry, 2020)
A highly enantioselective vinylogous Michael addition of 3-alkylidene-2-oxindoles with beta,gamma-unsaturated alpha-keto esters using a bifunctional tertiary-amine thiourea catalyst is demontsrated. The challenging Michael reaction with the beta,gamma-unsaturated alpha-keto esters has been accomplished due to the synchronized H-bond guided dual activation of vinylogous nucleophile and electrophile by catalyst. The reaction afforded product in high yield while resulting in excellent stereocontrol (> 19:1E/Zand upto 99 %ee).
Keywords: 3-Alkylidene-2-oxindoles; Asymmetric synthesis; beta; gamma-Unsaturated alpha-keto esters; Michael adduct; Vinylogous Michael addition

[1,3]-Claisen rearrangement via removable functional group mediated radical stabilization - Alam, Md Nirshad; Dash, Soumya Ranjan; Mukherjee, Anirban; Pandole, Satish; Marelli, Udaya Kiran; Vanka, Kumar; Maity, Pradip (Organic Letters, 2021)
A thermal O-to-C [1,3]-rearrangement of alpha-hydroxy acid derived enol ethers was achieved under mild conditions. The 2-aminothiophenol protection of carboxylic acids facilitates formation of the [1,3] precursor and its thermal rearrangement via stabilization of a radical intermediate. Experimental and theoretical evidence for dissociative radical pair formation, its captodative stability via aminothiophenol, and a unique solvent effect are presented. The aminothiophenol was deprotected from rearrangement products as well as after derivatization to useful synthons.

Computational insights into the role of external and local electric fields in macrocyclic chemical and biological systems - Mukherjee, Anagh; Ghule, Siddharth; Vanka, Kumar (ChemPhysChem, 2021)
The investigation of the role of the electric field in systems of widespread interest employing computational techniques is an emerging area of research. The outcome of applying an oriented external electric field (OEEF) on the geometric and electronic properties of the chemically unique pi-conjugated cyclic carbon ring compounds has been explored with density functional theory (DFT). Distinct changes in the structural and electronic features of such ring compounds are observed upon the application of OEEFs. Importantly, the calculations indicate that a mixed aliphatic-aromatic conjugated ring converts from a singlet to a triplet after the application of an OEEF, suggesting potential applications in optoelectronics for such molecules, without the need for photochemically induced change in the spin state. Furthermore, the influence of built-in local electric fields (LEFs) present in naturally occurring macrocyclic systems such as valinomycin has also been explored. Static and ab initio molecular dynamics (AIMD) calculations indicate that LEFs are the primary driving factor in determining the energetically favoured position of counter anions such as chloride (Cl-) in the potassium (K+) and sodium (Na+) coordinated valinomycin macrocycle structures: they exist inside the cage in the case of K+ sequestration by valinomycin and outside for Na+. This divergence has been proposed to be the determining factor for the selectivity of the valinomycin macrocycle for binding a K+ cation over Na+.
Keywords: counter anions; Density functional calculations; electric field; ion selectivity; macrocyclic systems

Deoxygenative hydroboration of primary and secondary amides: a catalyst-free and solvent-free approach - Kumar, Rohit; Bisai, Milan Kumar; Jain, Shailja; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
In contrast to the recent reports on catalytic hydroboration of amides to amines with pinacolborane (HBpin), a simple catalyst-free and solvent-free method for the hydroboration of a variety of amides has been realized. To get the mechanistic insights, DFT calculations have been performed.

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Diverse reactivity of hypersilylsilylene with boranes and threecomponent reactions with aldehyde and HBpin - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2021)
The recently reported hypersilylsilylene PhC-(NtBu)(2)SiSi(SiMe3)(3) (1) reacts with BH3, 9-BBN, and PhBCl2 to yield the respective Lewis acid base adducts 2-4, respectively. Compound 4 undergoes isomerization to form a ring expansion product 5. The same silylene was found to initially form an adduct with HBpin (6) and subsequently isomerized to 7 via the rupture of the B-H bond of HBpin (7), where the hydride was bound to the carbon atom of the amidinate ligand and the Bpin unit was attached to the silicon center. Surprisingly, the reaction of 1 with HBcat results in PhC(NtBu)(2)Bcat (8). Subsequently, we have shown that HBcat forms the same product when it reacts with related silylene PhC(NtBu)(2)SiN(SiMe3)(3) (1'). With all of these reactions in hand, we ponder if silylene can activate two small molecules at one time. In this work, we delineate the three-component reactions of silylenes 1 and 1' with 4-fluorobenzaldehyde and HBpin, which afforded unusual coupling products, 9 and 10, respectively. Note that 9 and 10 were prepared from the cleavage of the B-H and C=O bonds by silylene in a single reaction and are the first structurally attested Si-C-O-B coupled products.

Easy and practical approach to access multifunctional cylcopentadiene- and cyclopentene-spirooxindoles via [3+2] annulation - Warghude, Prakash K.; Sabale, Abhijeet S.; Dixit, Ruchi; Vanka, Kumar; Bhat, Ramakrishna G. (Organic & Biomolecular Chemistry, 2021)
A highly regioselective [3 + 2] annulation of Morita-Baylis-Hillman (MBH) carbonates of isatin with aurone/thioaurone is developed. Spiroheterocycles such as spirooxindole cyclopentadiene and spirooxindole fused hydroxy cyclopentene derivatives are constructed in one pot by exploring the reactivity of Lewis bases. Combined experimental and density functional theory (DFT) calculations offered an insight into the reaction mechanism.

Gold-catalyzed complementary nitroalkyne internal redox process: a DFT study - Vipin Raj, K.; Dhote, Pawan S. S.; Vanka, Kumar; Ramana, Chepuri V. V. (Frontiers in Chemistry, 2021)
Gold-catalysis, in this century, is one of the most emerging and promising new areas of research in organic synthesis. During the last two decades, a wide range of distinct synthetic methodologies have been unveiled employing homogeneous gold catalysis and aptly applied in the synthesis of numerous natural products and biologically active molecules. Among these, the reactions involving alpha-oxo gold carbene/alpha-imino gold carbene intermediates are of contemporary interest, in view of their synthetic potential and also due to the need to understand the bonding involved in these complexes. In this manuscript, we document the theoretical investigations on the regio-selectivity dependence of substitution on the gold-catalyzed cycloisomerization of o-nitroarylalkyne derivatives. We have also studied the relative stabilities of alpha-oxo gold carbene intermediates.
Keywords: alpha-Oxo Gold Carbene; cycloisomerization; DFT calculation; Gold-catalysis; internal redox

Insights into chemical reactions at the beginning of the universe: from HeH+ to H-3 (+) - Dash, Soumya Ranjan; Das, Tamal; Vanka, Kumar (Frontiers in Chemistry, 2021)
At the dawn of the Universe, the ions of the light elements produced in the Big Bang nucleosynthesis recombined with each other. In our present study, we have tried to mimic the conditions in the early Universe to show how the recombination process would have led to the formation of the first ever formed diatomic species of the Universe: HeH+, as well as the subsequent processes that would have led to the formation of the simplest triatomic species: H-3 (+). We have also studied some special cases: higher positive charge with fewer number of hydrogen atoms in a dense atmosphere, and the formation of unusual and interesting linear, dicationic He chains beginning from light elements He and H in a positively charged atmosphere. For all the simulations, the ab initio nanoreactor (AINR) dynamics method has been employed.
Keywords: ab initio molecular dynamics; ab initio nanoreactor; Density functional theory; origin of molecules in the universe; the earliest lewis acid

Insights into the nature of self-extinguishing external donors for ziegler-natta catalysis: a combined experimental and DFT study - Vipin Raj, K.; Kumawat, Jugal; Dhamaniya, Sunil; Subaramanian, Murugan; Balaraman, Ekambaram; Kumar Gupta, Virendra; Vanka, Kumar; Grubbs, Robert H. (ChemCatChem, 2021)
Developing donors for Ziegler-Natta (ZN) catalysis to control the polymerization reaction and produce polymers with desirable properties has always been challenging due to the multi-component nature of the catalytic systems. Here, we have developed a new synthetic protocol for making two external donors, D-1 (2,2,2-trifluoroethyl myristate) and D-2 (2,2,2-trifluoroethyl palmitate) that show self-extinguishing properties, followed by a systematic DFT study to understand this peculiar property of these donors. D-1 and D-2 can undergo parallel reactions with aluminum and titanium species present in the system to produce ketones and aldehydes, which are poisons for ZN catalytic systems, thus explaining their self-extinguishing nature. The non-covalent interaction between the long alkyl chain of the donors with the surface plays a vital role in determining the donors ` self-extinguishing nature. There is a significant thermodynamic preference for the binding of the donor with the longer alkyl chain at the titanium center. The current work, therefore, provides interesting insights into how self-extinguishing donors function in ZN catalytic systems.
Keywords: DFT; donors; non-covalent interactions; self-extinguishing; Ziegler-Natta catalysis

Lithium compound catalyzed deoxygenative hydroboration of primary, secondary and tertiary amides - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2021)
A selective and efficient route for the deoxygenative reduction of primary to tertiary amides to corresponding amines has been achieved with pinacolborane (HBpin) using simple and readily accessible 2,6-di-tert-butyl phenolate lithium center dot THF (1a) as a catalyst. Both experimental and DFT studies provide mechanistic insight.

Phosphite mediated asymmetric N to C migration for the synthesis of chiral heterocycles from primary amines - Rani, Soniya; Dash, Soumya Ranjan; Bera, Asish; Alam, Md Nirshad; Vanka, Kumar; Maity, Pradip (Chemical Science, 2021)
A phosphite mediated stereoretentive C-H alkylation of N-alkylpyridinium salts derived from chiral primary amines was achieved. The reaction proceeds through the activation of the N-alkylpyridinium salt substrate with a nucleophilic phosphite catalyst, followed by a base mediated [1,2] aza-Wittig rearrangement and subsequent catalyst dissociation for an overall N to C-2 alkyl migration. The scope and degree of stereoretention were studied, and both experimental and theoretical investigations were performed to support an unprecedented aza-Wittig rearrangement-rearomatization sequence. A catalytic enantioselective version starting with racemic starting material and chiral phosphite catalyst was also established following our understanding of the stereoretentive process. This method provides efficient access to tertiary and quaternary stereogenic centers in pyridine systems, which are prevalent in drugs, bioactive natural products, chiral ligands, and catalysts.

Readily available lithium compounds as catalysts for the hydroboration of carbodiimides and esters - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Journal of Organometallic Chemistry, 2021)
Selective and efficient hydroboration of esters and carbodiimides to alcohols and amines by two welldefined and readily accessible lithium complexes, 2,6-di-tert-butyl phenolate lithium (1a ) and 1,1'-dilithioferrocene (1b ) are described. A range of aliphatic, aromatic, and cyclic esters with various functional groups were selectively converted into the corresponding boronate esters. Similarly, the single hydroboration of carbodiimides with aliphatic and aromatic substituents on the nitrogen atoms was studied. A possible mechanistic pathway of the hydroboration of carbodiimides with HBpin has been proposed using NMR studies and DFT calculations. These reactions are convenient alternatives to stoichiometric hydride reduction or hydrogenation. The employing of lithium complexes is also significant, because of the need to find cheap and green alternatives to noble metal complexes. (C) 2021 Elsevier B.V. All rights reserved.

Substrate, catalyst, and solvent: the triune nature of multitasking reagents in hydroboration and cyanosilylation - Dixit, Ruchi; Bisai, Milan Kumar; Yadav, Sandeep; Yadav, Vinita; Sen, Sakya S.; Vanka, Kumar (Organometallics, 2021)
A truly green chemical process would avoid the use of an external catalyst, while still achieving high efficiency. This has been realized in the very recent past for hydroboration, cyanosilylation, acetalization, and the aza-Michael addition, among other reactions. The current combined computational and experimental study unlocks the secret to how this highly desirable outcome is accomplished: one of the reactants in the process also acts as the catalyst. Specifically, this is shown (i) for the important hydroboration reaction, with pinacolborane (HBpin) as the hydroborating reagent and benzaldehyde, acetophenone, benzoic acid and p-methoxyphenylacetylene as the hydroborated substrates, and (ii) for cyanosilylation, with trimethylcyanosilane (TMSCN) as the cyanosilylating agent and benzaldehyde as the substrate. The mechanistic understanding thus gained has then been further exploited experimentally to bring hydroboration and cyanosilylation closer to experimental conditions in catalysis. These insights can potentially be expanded to the rapidly growing area of solvent-free and internal catalyst chemistry.

Synthesis of four diastereomers of notoryne and their C-13 NMR chemical shifts analysis - Senapati, Sibadatta; Das, Shyamsundar; Dixit, Ruchi; Vanka, Kumar; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
In this manuscript we document the details of the synthesis of four diastereomers of notoryne. The synthesis of one of the diastereomer having a similar relative stereochemistry of substituents on the both THF rings like notoryne, however, being the relative stereochemistry between the bridging carbon of these two THF units is changed from anti to syn has been executed mainly to learn how the ring carbon chemical shifts vary with this change. Interestingly, the deviations are found mainly for the carbons of THF ring that bears the Br-group. In addition to this isomer, three more diastereomers having the relative stereochemistry of substituents on either of the THF rings varied have been also synthesized. All four diastereomers have been subjected for extensive NMR studies and their C-13 NMR chemical shifts have been compared with notoryne and laurendecumenyne B. In addition, chemical shifts for the four diastereomers along with these natural products were calculated with the help of DFT calculations and compared to the experimentally obtained chemical shift values.

Total synthesis of the pseudoindoxyl class of natural products - Dhote, Pawan S.; Patel, Pitambar; Vanka, Kumar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2021)
The pseudoindoxyl sub-structural motif, amongst the large set of the indole class of alkaloids, represents a unique subset of the oxygenated indole class of the alkaloid family. A majority of this class of natural products contains complex bridged/polycyclic scaffolds with interesting biological profiles. They are thus attractive synthetic targets. Starting from 1963, twenty-eight natural products having the pseudoindoxyl scaffold have been isolated, among which the synthesis of 13 natural products has been accomplished. In this review, we highlight the completed as well as the formal total synthesis of the natural products with a spiro-pseudoindoxyl ring, with a focus on their development. The challenges and the future perspective based on the recent developments in the field will also be discussed. We strongly believe that this review will not only update but also attract the attention of researchers in dealing with the synthesis of pseudoindoxyl compounds.

Unsymmetrical sp(2)-sp(3) disilenes - Bisai, Milan Kumar; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2021)
Disilenes with differently coordinated silicon atoms are not known. Here, we have shown the high yield synthesis of a range of disilenes (2-4 and 6) upon reaction of a hypersilyl silylene PhC(NtBu)(2)SiSi(SiMe3)(3) (1) with aliphatic chlorophosphines. The most striking characteristic of these disilenes is the presence of two differently coordinated Si atoms (one is three-coordinated, the other four-coordinated). The analogous reaction with Ph2PCl did not afford the desired disilene, but, surprisingly, led to the first tetraphosphinosilane (8). DFT calculations were performed to understand the bonding in disilenes and differences in reactivity of the complexes.
Keywords: chlorophosphine; DFT; disilene; hypersilylsilylene

Antimicrobial two-dimensional covalent organic nanosheets (2D-CONs) for the fast and highly efficient capture and recovery of phosphate ions from water - Dey, Subhasis; Das, Sribash; Patel, Anjali; Raj, K. Vipin; Vanka, Kumar; Manna, Debasis (Journal of Materials Chemistry A, 2022)
The retrieval of depleting resources from wastewater could help resolve the mounting demands for resources in our society. Phosphate is an essential nutrient for all living things. However, the diminution of global reserves of phosphate rock could significantly affect our food security in the near future. At the same time, the removal of phosphates and pathogens is of great importance for water security and de-eutrophication. The specific pH-dependent adsorption and desorption of phosphate ions by water-insoluble adsorbents is an exciting strategy for removing and recovering phosphates from contaminated water. Herein, we report the development of new two-dimensional guanidine-containing covalent organic nanosheets (2D-gCONs). This water-insoluble amorphous polymer (exfoliated) selectively sequestered phosphate ions in the presence of other competing anions and could be reused for multiple cycles. The polymer showed a fast removal of phosphate ions with a maximum adsorption capacity of 398 mg g(-1) (pH 7.0). The sequestered phosphate ions could be easily reclaimed, and the polymer could be recycled just by altering the pH (similar to 10.0) of the aqueous solution. The guanidinium moieties played a pivotal role in exfoliation in aqueous medium and in the antibacterial activities against Gram-negative and Gram-positive bacteria. We hypothesize that the current study may advance the design of water-insoluble CONs to remove and recover phosphate ions from wastewater and could help alleviate the negative impact of water eutrophication. This strategy can also be tweaked to address other severe environmental challenges.

Computational insights into hydroboration with acyclic alpha-Borylamido-germylene and stannylene catalysts: Cooperative dual catalysis the key to system efficiency - Banerjee, Subhrashis; Vanka, Kumar (Polyhedron, 2022)
The chemistry of low valent main group compounds has grown as an alternative to the chemistry of less abundant and less green transition metal complexes. It has been found that low valent compounds such as carbenes, silylenes, stannylenes and germylenes are efficient for activating small molecules and for catalysis. However, the reaction mechanism and the factors that affect the rate of reaction are not completely understood. In this computational investigation with density functional theory (DFT), we investigate and demonstrate the efficiency of a new mechanism for the hydroboration of aldehydes by germylenes and stannylenes, in the presence of the common hydroborating agent, pinacolborane, HBpin. This mechanism involves an HBpin molecule as an additional catalyst that cooperates with the germylene or stannylene catalyst to efficiently carry out the hydroboration. This mechanism is first demonstrated to work for experimentally reported systems, and then shown to be efficient for newly proposed germylene and stannylene systems. These new systems are alpha-Borylamido-germylene ((2,6-iPr(2)C(6)H(3)NBCy(2))(2)Ge(II)) and alpha-Borylamido-stannylene((2,6-iPr(2)C(6)H(3)NBCy(2))(2)Sn(II)). These new insights will help researchers look into low valent germylene and stannylene chemistry from a new perspective.
Keywords: Catalysis of hydroboration; computational chemistry; Germylenes and stannylenes; Main group chemistry; New mechanism

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Direct oxidation of bromo-derived Fischer-Borsche oxo-ring using molecular iodine with combined experimental and computational study - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2022)
A direct oxidation of the bromo-derived Fischer-Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.

Enantioselective Cu(I)-catalyzed borylative cyclization of enone-tethered cyclohexadienones and mechanistic insights - Jadhav, Sandip B.; Dash, Soumya Ranjan; Maurya, Sundaram; Nanubolu, Jagadeesh Babu; Vanka, Kumar; Chegondi, Rambabu (Nature Communications, 2022)
Rapidly building molecular structures with both elements of complexity and flexibility is a key goal of organic synthesis. Here the authors show a tandem copper-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones, to generate bicyclic borylated products in high yield and enantioselectivity. The catalytic asymmetric borylation of conjugated carbonyls followed by stereoselective intramolecular cascade cyclizations with in situ generated chiral enolates are extremely rare. Herein, we report the enantioselective Cu(I)-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones. This asymmetric desymmetrization strategy has a broad range of substrate scope to generate densely functionalized bicyclic enones bearing four contiguous stereocenters with excellent yield, enantioselectivity, and diastereoselectivity. One-pot borylation/cyclization/oxidation via the sequential addition of sodium perborate reagent affords the corresponding alcohols without affecting yield and enantioselectivity. The synthetic potential of this reaction is explored through gram-scale reactions and further chemoselective transformations on products. DFT calculations explain the requirement of the base in an equimolar ratio in the reaction, as it leads to the formation of a lithium-enolate complex to undergo C-C bond formation via a chair-like transition state, with a barrier that is 22.5 kcal/mol more favourable than that of the copper-enolate complex.

Luminescent magnesium complexes with intra- and inter-ligand charge transfer - Kumar, Rohit; Pahar, Sanjukta; Chatterjee, Joy; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we report two 2,2'-pyridylpyrrolide (PyPyrH) ligand supported magnesium complexes (1 and 2), which demonstrate bright luminescence with a quantum yield of 22% and 14% in the solid state, respectively. Theoretical calculations reveal that their emissive properties originate from the intra- and inter-ligand charge transfer.

Mechanistically guided one pot synthesis of phosphine-phosphite and its implication in asymmetric hydrogenation - Sen, Anirban; Kumar, Rohit; Pandey, Swechchha; Raj, K. Vipin; Kumar, Pawan; Vanka, Kumar; Chikkali, Samir H. (European Journal of Organic Chemistry, 2022)
Although hybrid bidentate ligands are known to yield highly enantioselective products in asymmetric hydrogenation (AH), synthesis of these ligands is an arduous process. Herein, a one pot, atom-economic synthesis of a hybrid phosphine-phosphite (L1) is reported. After understanding the reactivity difference between an 0-nucleophile versus C-nucleophile, one pot synthesis of Senphos (L1) was achieved (72%). When L1 was treated with [Rh], P-31 NMR revealed bidentate coordination to Rh. Senphos, in the presence of rhodium, catalyzes the AH of Methyl-2-acetamido-3-phenylacrylate and discloses an unprecedented turn over frequency of 2289, along with excellent enantio-selectivity (92%). The generality is demonstrated by hydrogenating an array of alkenes. The AH operates under mild conditions of 1-2 bar H-2 pressure, at room temperature. The practical relevance of Ll is demonstrated by scaling-up the reaction to 1 g and by synthesizing DOPA, a drug widely employed for the treatment of Parkinson's disease. Computational insights indicate that the R isomer is preferred by 3.8 kcal/mol over the S isomer.
Keywords: asymmetric hydrogenation; catalysis; DOPA synthesis; One pot synthesis; Phosphine-phosphite ligand

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Predicting the redox potentials of phenazine derivatives using DFT-assisted machine learning - Ghule, Siddharth; Dash, Soumya Ranjan; Bagchi, Sayan; Joshi, Kavita; Vanka, Kumar (ACS Omega, 2022)
This study investigates four machine-learning (ML) models to predict the redox potentials of phenazine derivatives in dimethoxyethane using density functional theory (DFT). A small data set of 151 phenazine derivatives having only one type of functional group per molecule (20 unique groups) was used for the training. Prediction accuracy was improved by a combined strategy of feature selection and hyperparameter optimization, using the external validation set. Models were evaluated on the external test set containing new functional groups and diverse molecular structures. High prediction accuracies of R2 > 0.74 were obtained on the external test set. Despite being trained on the molecules with a single type of functional group, models were able to predict the redox potentials of derivatives containing multiple and different types of functional groups with good accuracies (R2 > 0.7). This type of performance for predicting redox potential from such a small and simple data set of phenazine derivatives has never been reported before. Redox flow batteries (RFBs) are emerging as promising candidates for energy storage systems. However, new green and efficient materials are required for their widespread usage. We believe that the hybrid DFT-ML approach demonstrated in this report would help in accelerating the virtual screening of phenazine derivatives, thus saving computational and experimental costs. Using this approach, we have identified promising phenazine derivatives for green energy storage systems such as RFBs.

Reactivity of four coordinate iridium complex towards hydrogen: an experimental and computational study - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Nethaji, Munirathinam; Jagirdar, Balaji R. (Journal of Organometallic Chemistry, 2022)
Reaction of a four coordinate, 16-electron Ir complex, [Ir-(iPr)4(POCOP)(PPh3)] (4 ) (((iPr)4)(POCOP= 2,6-bis(di-isopropyl phosphinito)benzene, kappa(3)-C6H3-1,3-[OP((iPr))(2)](2)), with H-2 resulted in an oxidative addition product, cis-dihydride complex, cis-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( cis-5 ) presumably via the intermediacy of a sigma complex, [Ir(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)]. The cis-dihydride complex completely isomerizes to the trans-dihydride complex trans-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( trans-5 ) under ambient conditions in about 3 h. It was found that the steric and electronic features on the iridium center have significant influence on the approach of H-2 onto the metal center followed by oxidative addition and isomerization. The isomerization process was studied in detail and all the mechanistic aspects have been elucidated using a combination of both experimental work and computation. The cis-dihydride complex isomerizes to the trans-dihydride by compensating the trans influence of the strongly trans-directing hydride ligand. A mechanism involving the exchange of the position of PPh3 with a hydride ligand cis to itself via PPh3 dissociation and re-coordination thereby resulting in the formation of the trans-dihydride complex, has been proposed for the isomerization. The cis-dihydride was found to be a highly active catalyst for hydrogenation of ethy-lene. A competing reactivity study of cis-dihydride between isomerization versus insertion of C2H4 into the Ir-H bond, was studied experimentally and computationally. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Insertion; iridium complex; isomerization; Oxidative addition; Reductive elimination

Room temperature chemoselective hydrogenation of C=C, C=O and C=N bonds by using a well-defined mixed donor Mn(I) pincer catalyst - Shabade, Anand B.; Sharma, Dipesh M.; Bajpai, Priyam; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Chemical Science, 2022)
Chemoselective hydrogenation of C=C, C=O and C=N bonds in alpha,beta-unsaturated ketones, aldehydes and imines is accomplished at room temperature (27 degrees C) using a well-defined Mn(I) catalyst and 5.0 bar H-2. Amongst the three mixed-donor Mn(I) complexes developed, kappa(3)-((PNNPyz)-P-R2-N-3)Mn(CO)(2)Br (R = Ph, Pr-i, Bu-t); the Bu-t -substituted complex ((PNNPyz)-P-tBu2-N-3)Mn(CO)(2)Br shows exceptional chemoselective catalytic reduction of unsaturated bonds. This hydrogenation protocol tolerates a range of highly susceptible functionalities, such as halides (-F, -Cl, -Br, and -I), alkoxy and hydroxy, including hydrogen-sensitive moieties like acetyl, nitrile, nitro, epoxide, and unconjugated alkenyl and alkynyl groups. Additionally, the disclosed method applies to indole, pyrrole, furan, thiophene, and pyridine-containing unsaturated ketones leading to the corresponding saturated ketones. The C=C bond is chemoselectively hydrogenated in alpha,beta-unsaturated ketones, while the aldehyde's C=O bond and imine's C=N bond are preferentially reduced over the C=C bond. A detailed mechanistic study highlighted the non-innocent behavior of the ligand in the ((PNNPyz)-P-tBu2-N-3) Mn(I) complex and indicated a metal-ligand cooperative catalytic pathway. The molecular hydrogen (H-2) acts as a hydride source, whereas MeOH provides a proton for hydrogenation. DFT energy calculations supported the facile progress of most catalytic steps, involving a crucial turnover-limiting H-2 activation.

Silver dependent enantiodivergent gold(i) catalysed asymmetric intramolecular hydroamination of alkenes: a theoretical study - Dixit, Ruchi; Sharma, Himanshu; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysts, 2022)
We report a theoretical study of the first silver-dependent enantiodivergent gold-catalysed reaction. The combination of a single chiral binuclear gold(I) chloride complex and silver perchlorate catalyses the asymmetric intramolecular hydroamination of alkenes and affords both enantiomers of the products by applying a simple solvent change from toluene to methanol. A gold-silver chloride adduct that occurs only in methanol appears to control the enantioinversion. If one gold atom coordinates and activates the alkene moiety, the other gold is included in an adduct with silver chloride, which coordinates a methanol solvent molecule and further interacts with the amine function. If the use of toluene implies free anions and affords (S)-enantiomer, methanol allows a proximal interaction with the amine, leads to an opposite stereodifferentiation of the two diastereomeric intermediates during the final protodeauration step and results in the (R)-enantiomer.
Keywords: alkene; enantiodivergent catalysis; Gold; hydroamination; Silver

Silver-catalyzed [3 + 3]-annulation cascade of alkynyl alcohols and α,β-unsaturated ketones for the regioselective assembly of chromanes - Nakate, Ashwini K.; Thorat, Sagar S.; Jain, Shailja; Rama Krishna, Gamidi; Vanka, Kumar; Kontham, Ravindar (Organic Chemistry Frontiers, 2022)
An unprecedented Ag(i)-catalyzed [3 + 3]-annulation of alkynyl alcohols (5-hexyn-1-ols) and α,β-unsaturated ketones is reported to construct simple to complex chromanes. This transformation begins with hydroalkoxylation of alkynol through C–C triple bond activation to give cyclic-enol ether, followed by intermolecular 1,4-addition and intramolecular 1,2-addition of enol ethers onto the enone and oxidative aromatization or Grob-type elimination steps. Facile reaction conditions, broad substrate scope, good to excellent yields, and atom economy are the salient features of this protocol. Isolation of the active pyran-tethered cyclohexadiene reaction intermediate, additional supporting experiments, and DFT calculations strongly support the experimental findings and corroborate our proposed mechanism.

Substitution at sp(3) boron of a six-membered NHC center dot BH3: convenient access to a dihydroxyborenium cation - Kundu, Gargi; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we have undertaken the synthesis and investigated the reactivity of a 6-membered saturated NHC borane adduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I-2 led to NHC boryl iodides, 6-SIDipp center dot BH2I (2) and 6-SIDipp center dot BHI2 (3), which were further reacted with various nucleophiles to give novel 6-SIDipp based mono and disubstituted boranes with OTf (4 and 6) or ONO2 (5 and 7) functional groups. The addition of Br-2/H2O to 1 smoothly results in a dihydroxyborenium cation (8).

Tridentate NacNac stabilized tin and nickel complexes: access to a monomeric nickel hydride and its catalytic application - Pahar, Sanjukta; Sharma, Vishal; Mahata, Biplab; George, Christy P.; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2022)
The transmetalation reaction of picolyl-supported tridentate nacnac germylene monochloride [2,6-iPr2-C6H3NC-(Me)CHC(Me)NH(CH2py)]GeCl (1) (py = pyridine) with SnCl2 results in an analogous stannylene chloride (2). The three -coordinated stannylenium cation [{2,6-iPr2-C6H3NC(Me)CHC-(Me)NH(CH2py)}Sn]+ with SnCl3- as a counteranion (3) has been generated through the abstraction of chloride ligand from 2 using an additional equivalent of SnCl2. Instead of forming a donor-acceptor complex, 2 undergoes a facile redox trans-metalation reaction with Ni(COD)2 (COD = cyclooctadiene) and CuCl to afford analogous nickel and copper complexes [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]MCl [M = Ni (4) and Cu (5)]. The reactions of 4 with potassium tri-sec-butylborohydride (commonly known as K-selectride) and AgSbF6 provide access to monomeric Ni(II) hydride, [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]NiH (6) and a Ni(II) cation, [{2,6-iPr2- C6H3NC(Me)CHC(Me)NH(CH2py)}Ni][SbF6] (7), respectively. 6 was found to be an effective catalyst for the hydroboration of amides.

Versatile chemistry of six-membered NHC with boranes: bromination at sp(3) borane, activation of the B-H bond of HBpin, and ring expansion of NHC - Kundu, Gargi; Dixit, Ruchi; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2022)
The NHC.borane chemistry has been majorly restricted to imidazol-2-ylidene classes of carbenes. In our previous communication, we reported the synthesis of 6-SIDipp center dot BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene] and its electrophilic substitution reaction with iodine. Here, we have shown selective bromination of a 6-SIDipp stabilized sp(3) B-H bond. Treatment of 1.2 equivalents of N-bromosuccinamide with 6-SIDipp center dot BH3 gives a mixture of mono- and disubstituted products 6-SIDipp center dot BH2Br (1) and 6-SIDipp center dot BHBr2 (2). However, the reactions with alkyl bromides or carbon tetrabromide resulted in 6-SIDipp center dot BH2Br (1) selectively. Exploration of the chemistry of 6-SIDipp with BHCl2 and 9-BBN (9-borabicyclo[3.3.1]nonane) led to mono-6-SIDipp adducts 3 and 6a. Furthermore, 6a undergoes ring expansion to afford a seven-membered product, 6b, under mild conditions. Unlike BHCl2 or 9-BBN, the B-H bond of HBpin undergoes oxidative addition upon reaction with 6-SIDipp, epitomizing the first example (7) of a B-H bond insertion at NHCs. The analogous reactivity with HBcat led to a tetra-hydropyrimidinium salt with B(cat)(2) as a counteranion (8).

Well-defined calcium compound catalyzes trimerization of arylisocyanates into 1,3,5-triarylisocyanurates - Kumar, Rohit; Sharma, Vishal; Jain, Shailja; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (ChemCatChem, 2022)
We report the synthesis of a calcium complex (2) bearing a tetradentate monoanionic ligand with a diaminoethane core and phenolate and pyridine peripheral donors. Single crystal X-ray studies on 2 revealed that LiI was also co-crystallized, leading to a four-membered ring with four different elements. 2 was found to be an efficient catalyst for the cyclotrimerization of a variety of aromatic isocyanates under mild conditions.
Keywords: calcium; Cyclotrimerization; Isocyanurates; Tetradentate ligand

Activation of the olefinic C-H bond of NHC and NHO by perimidine-based silicon and germanium compounds - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2023)
In this manuscript, several backbonegermylene-functionalized zwitterioniccompounds were prepared conveniently from the corresponding N-heterocycliccarbenes or N-heterocyclic olefins in a single step through backboneC-H activation. Our initial motivation was to generate a silylenefrom C10H6(Me3SiN)(2)SiHCl(2) using ItBu [ItBu= (1,3-ditert-butyl)imidazol-2-ylidene], but instead, the reactionled to deprotonation from the imidazolium backbone of ItBu, forming the imidazolium salt with a silyl backbone at the C4position (3). We presumed that the reaction proceededthrough the generation of an ephemeral silylene. We subsequently preparedthe analogous germylene (4) and reacted it with IDipp[IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], ItBu, and IDipp=CH2. Spectroscopic and crystallographicanalysis of these complexes revealed that, in all cases, there wasdeprotonation from the backbone and formation of zwitterionic products(5-7). When the hydrogen in the NHCbackbone was replaced with methyl groups such as IDipp(Me) (1,3-bis(2,6-diisopropylphenyl)-4,5-dimethylimidazol-2-ylidene),simple adduct formation occurred, exemplified by the isolation ofIDipp(Me)& BULL;Ge(NSiMe3)(2)C10H6 (8).

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst

Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.

Dual routes toward observation of a trans-H2/hydride complex in an iridium pincer system and hydrogenation catalytic activity - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Organometallics, 2023)
The Abstraction of chloride from a six- coordinate complex, trans-[ Ir(H)(Cl)((iPr)4)(POCOP)(PPh3)] (1) [((iPr)4)(POCOP) = 2,6-bis(di-iso-propylphosphinito)benzene,kappa(3)-C6H3-1,3-[OP(Pr-i)(2 )](2)], using NaBAr4f leads to the generation of a dinitrogen complex, trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6). Addition of H-2 to [Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) (6) under extremely mild conditions (1 bar, 298 K) resulted in the reversible coordination of H-2 to generate the cis-[Ir(H)(eta H-2-(2))((iPr)4)(POCOP)(PPh3)](+) (cis-11) complex. The cis-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (cis-11) isomerized to a trans isomer, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11), at 253 K. The isomerization process has been studied and supported by computations. Employing an alternative route, protonation of the trans-[Ir(H)(2)((iPr)4)(POCOP)(PPh3)] complex (2) at 183 K resulted in the formation of an identical, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (trans-11); upon warming the sample, the trans-H-2/hydride complex isomerized to the cis isomer above 253 K. Two independent routes to obtain trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11) species have been established. Reaction of trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6) with C2H4 gave the cis-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complex (cis-15), which also undergoes isomerization to yield an equilibrium mixture of cis/trans-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complexes (cis-15 and trans-15) at 253 K. The trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) complex (6) is an excellent catalyst for hydrogenation of ethylene to ethane under very mild conditions.

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

H-atom site exchange in an iridium trans-dihydrogen/hydride complex, trans-[Ir(H)(?2-H2)(iPr)4(POCOP)(DMAP)]+ - Agrawal, Nisha K.; Gayathridevi, S.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Dalton Transactions, 2023)
Treatment of trans-[Ir(H)(N)(2)((iPr)4)(POCOP)(DMAP)][BAr4f] (2) with H-2 (1 bar) under ambient conditions (298 K) results in the formation of a trans-[Ir(H)(?(2)-H-2)((iPr)4)(POCOP)(DMAP)][BAr4f] (3) complex. Complex 3 exhibits H-atom site exchange between the bound H-2 and the hydride ligands which are mutually trans to one another. A plausible mechanism of this exchange involves metal-ligand cooperativity as studied by computations.

Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation

Potential role of lewis acid-base adducts in enhancing stereoselectivity in ziegler-natta catalysts: a DFT study - Raj, K. Vipin; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2023)
Ziegler-Natta (Z-N) systems have been well established as heterogeneous catalysts that produce isotactic polypropylene and polyethylene with great efficiency. Such systems benefit considerably from donors (Lewis bases), whose addition significantly improves the stereoselectivity of polymerization. There is a consensus that the primary role of the external donors is to coordinate at the vacant site created by the extraction of internal donors and thus maintain the stereoselectivity. However, the bite difference between internal donors such as phthalates or succinate derivatives and external donors such as alkoxysilanes raises the question of how external donors can effectively replace internal donors. In order to investigate this, we have chosen four external alkoxysilane donors: (1) diisopropyl dimethoxysilane, (2) dicyclopentyl dimethoxysilane, (3) disec-butyl dimethoxysilane, and (4) sec-butyl(methyl) dimethoxysilane. DFT studies reveal that the bite difference problem can be overcome by the favorable formation of adducts between the alkoxysilane external donors and AlEt2Cl in the Z-N systems. These adducts tend to coordinate in the vicinity of the active site. Furthermore, our findings demonstrate the potential of these Lewis acid-base adducts to enhance the stereoselectivity of Z-N catalysts significantly.

Rivaroxaban eutectics with improved solubility, dissolution rates, bioavailability and stability - Shaligram, Parth S.; George, Christy P.; Sharma, Himanshu; Mahadik, Kakasaheb R.; Patil, Sharvil; Vanka, Kumar; Arulmozhi, S.; Gonnade, Rajesh G. (Crystengcomm, 2023)
Rivaroxaban (RXB) is a direct factor Xa inhibitor used for the treatment of deep vein thrombosis (DVT, a blood clot in the leg) and pulmonary embolism (PE, a blood clot in the lung) and to prevent blood clots in atrial fibrillation following hip or knee surgery. However, RXB suffers from poor solubility that hinders its broader application. Although its cocrystals are reported for solubility enhancement, the methodology used to prepare multi-component crystals is complex. Also, it uses hazardous solvents to develop cocrystals. We have prepared eutectics of RXB with caffeic acid (CAA), coumaric acid (CA), fumaric acid (FA), succinic acid (SA), mandelic acid (MA) and trimesic acid (TA) and analyzed them using hot stage microscopy (HSM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and fourier transform infrared spectroscopy (FTIR) techniques. The saturation solubility and dissolution rate profiles were also obtained to investigate the effect of eutectics on these parameters. Amongst all the coformers tested, coformers CAA, CA, and FA showed significant enhancement in the solubility of RXB. The powder dissolution rate of the eutectics showed considerable enhancement compared to that of RXB. In vivo pharmacokinetic study was carried out for RXB-CAA, RXB-CA and RXB-FA in rats and compared with RXB, which showed 1.5 and 1.4 times enhancement in relative bioavailability for RXB-CAA and RXB-CA, respectively. Stability studies were carried out as per ICH guidelines for all the eutectics, which revealed excellent stability over six months under accelerated (40 degrees C and 75%) conditions and twelve months under long-term (30 degrees C and 60% RH) conditions. The DFT studies carried out using the B3LYP/TZVP level of theory revealed higher Gibbs free interaction energy (Delta G(int)) for homosynthons (drugMIDLINE HORIZONTAL ELLIPSISdrug and coformerMIDLINE HORIZONTAL ELLIPSIScoformer) than heterosynthons (drugMIDLINE HORIZONTAL ELLIPSIScoformer).

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Synthesis, characterization, crystal structure, in silico and computational studies on a novel Schiff base derived from α-chlorocinnamaldehyde and 4-aminoantipyrine - Adimudo, Hillary Chijioke; Agu, Chidike Justus; Okenyeka, Obinna U.; Eddy, Nnabuk O.; Dim, Ebubechukwu Nnamdi; Dege, Necmi; Bonardd, Sebastian; Vanka, Kumar; Ibezim, Akachukwu; Idika, Digbo Iku; Diaz, David Diaz; Obasi, Nnamdi Lawrence (Journal of Molecular Structure, 2023)
Schiff base, 4-(((1E,2Z)-2-chloro-3-phenylallylidene)amino)-1,5-dimethyl-2-phenyl-1,2 -dihydro-3H-pyrazol-3-one (1) was synthesized by condensation reaction of 4-aminoantipyrine and & alpha;-chlorocinnamaldehyde. The compound was characterized using Fourier-transform infrared spectroscopy (FT-IR), ultraviolet (UV)-visible spectroscopy, proton and carbon nuclear magnetic resonance spectroscopy (1H/13C NMR) and single-crystal X-ray diffraction analysis (SC-XRD). Density functional theory (DFT) was used to compute molecular parameters and also compared them with experimental data. The X-ray diffraction data revealed that the compound crys-tallizes as a monoclinic crystal system with a space group of C2/c and Z = 8, and is stabilized by C12-H12MIDLINE HORIZONTAL ELLIPSISO1, and C8-H8AMIDLINE HORIZONTAL ELLIPSISO1 intramolecular hydrogen bonds. The presence of a distinctive azomethine C = N bond length N3-C12 of 1.283(3) & ANGS;, and 1640 cm-1 stretching vibration in the FT-IR spectrum are evidence of the formation of a Schiff base. The computational result indicates that the ionization energy (IE), and electron affinity (EA) values for the molecule are 4.025 and 2.110 eV, respectively. The positive value of EA suggests that the addition of an electron to the molecule would be an exothermic process. The evaluated energy is relatively low and is an expression of the ease of electron transfer from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). Hirsfeld surface map over dnorm and curvedness surface indicated the presence of 7C-7C stacking while the shape factor index suggests donor and acceptor intermolecular C-H-7C. Analysis of Hirsfeld surfaces concerning the fingerprint indicated a minimal contribution from the de -di pair and reveals H–H as a major contribution to the Hirsfeld surface. However, the molecular packing did not confirm H–H as a significant contributor the packing. Docking calculations on the compound showed average theoretical binding energies toward aromatase (-5.99 & PLUSMN; 0.34 kcal/mol) and fibroblast growth factor receptor (FGFR) (-17.57 & PLUSMN; 6.85 kcal/mol), indicating binding interactions with both protein targets.
Keywords: Computational studies; molecular modeling; Schiff base; X-ray crystallography

Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.

Taming the parent oxoborane - Kundu, Gargi; Amrutha, P. R.; Raj, K. Vipin; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Chemical Science, 2023)
Despite recent advancements in the chemistry of multiply bound boron compounds, the laboratory isolation of the parent oxoborane moiety, HBO has long remained an unsolved and well-recognized challenge. The reaction of 6-SIDipp(.)BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl)tetrahydropyrimidine2-ylidene] with GaCl3 afforded an unusual boron-gallium 3c-2e compound (1). The addition of water to 1 resulted in the release of H-2 and the formation of a rare acid stabilized neutral parent oxoborane, LB(H)]O (2). Crystallographic and density functional theory (DFT) analyses support the presence of a terminal B=O double bond. Subsequent addition of another equivalent of water molecule led to hydrolysis of the B-H bond to the B-OH bond, but the `B=O' moiety remained intact, resulting in the formation of the hydroxy oxoborane compound (3), which can be classified as a monomeric form of metaboric acid.

Visible-light-active unsymmetrical squaraine dyes with 1 V of open-circuit voltage for dye-sensitized solar cells - Singh, Amrita; Kumar Singh, Ambarish; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ChemPhotoChem, 2023)
A series of alkyl-group-functionalized, aniline- and indoline-donor-based, unsymmetrical visible-light-active squaraine dyes, AM1-3, were designed and synthesized. Dye-sensitized solar cell (DSSC) devices were fabricated with both I-/I-3(-) and [Cu(tmby)(2)](+/2+) electrolytes. DSSC devices sensitized with the AM1 and AM2 dyes showed relatively high-power conversion efficiency of 7.44 % and 7.22 %, respectively with I-/I-3(-) in the absence of chenodeoxycholic acid (CDCA) than those of the AM3 dye (5.41 %). The [Cu(tmby)(2)](+/2+) electrolyte along with poly(3,4-ethylenedioxythiophene) (PEDOT) as cathode material showed excellent open-circuit potentials (V-OC) of 1030, 1025, and 1001 mV with the DSSC efficiency of 8.05 %, 7.96 %, and 5.84 %, respectively, for the AM1, AM2, and AM3 dyes in the absence of CDCA. Here, the AM1 dye exhibited the maximum DSSC efficiency of 8.05 % and V-OC of 1030 mV, which is the highest obtained efficiency and V-OC for the visible-light active zwitterionic unsymmetrical-squaraine dye with copper-based electrolyte.
Keywords: Cu electrolytes; dihedral angle; Dye-sensitized solar cells; open circuit voltage; squaraine dyes

"Weak" C-H•••S interaction drives enantioselectivity in cinchona alkaloid complex catalyzed thiocyanation - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-An Asian Journal, 2023)
The great success of asymmetric organocatalysis has made it one of the most important advancements made in chemistry in the past two decades. A significant achievement in this context is the asymmetric organocatalysis of the thiocyanation reaction. In the current study, computational studies with density functional theory have been done in order to understand an interesting experimental finding: the reversal of enantioselectivity from R to S when the electrophile is changed from beta-keto ester to oxindole for the thiocyanation reaction with the cinchona alkaloid complex catalyst. The calculations reveal an unusual fact - the principal reason for the reversal is the presence of the C-H center dot center dot center dot S noncovalent interaction, which is present only in the major transition states in each of the two nucleophile cases. Only recently has it been realized that the supposedly weak C-H center dot center dot center dot S noncovalent interaction has the properties of a hydrogen bond, and the fact that this interaction is the cause of enantioselectivity has relevance, because of the large number of asymmetric transformations involving the sulphur heteroatom.
Keywords: Density functional calculations; Enantioselectivity; noncovalent interactions; organocatalysis; reaction mechanisms

Zwitterionic disilanylium from an unsymmetrical disilene - Bisai, Milan Kumar; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The reaction of PhC(NtBu)2SiSi(SiMe3)(3) (1) with Me3SiCH(2)Cl afforded an unsymmetrical sp(2)-sp(3) disilene, 2, with concomitant elimination of Me3SiCl. The analogous reaction with PhC(NtBu)2SiCl resulted in the oxidative addition of the C-Cl bond at the Si(II) atom (3). The reactions of 2 with sulfur and selenium led to compounds with Si=E (E=S (4) and Se (5)) double bonds. Tellurium reacted differently with 2 and furnished a zwitterionic compound, 6.

Zwitterionic tetrastanna(II) cyclic crown - Sahoo, Padmini; Chibde, Purva; Das, Satyabrata; Banerjee, Subhrashis; Mali, Bhupendra P.; Vanka, Kumar; Gonnade, Rajesh G.; Yildiz, Cem. B.; Majumdar, Moumita (European Journal of Inorganic Chemistry, 2023)
A 12-membered zwitterionic tetrastanna(II) cycle 1 having a crown ether-like topology has been isolated from the deprotonation of 1,1 & PRIME;-methylenediimidazole (B) with two equivalents of Sn[N(SiMe3)(2)](2) (A). The solid-state structure and NMR analysis confirms the tetrastanna(II) cycle 1 to be comprised of two stannate(II) and two stannyliumylidene ion pairs in alternating positions of the heterocycle. Computational analysis shows greater nucleophilicity at the proximally located stannate(II) centers. Nonetheless, the tetrastanna(II) cycle 1 remains poorly reactive due to engagement of Sn-II lone pair electrons in intramolecular donor-acceptor interactions. Simple deprotonation reaction between Sn[N(SiMe3)(2)](2) (A) and N-(diisopropylphenyl)imidazole (C) in equimolar ratio has led to a stannylene 2, involving the formation of a Sn-C covalent bond with the anionic imidazol-2-yl carbon center along with the release of NH(SiMe3)(2). Compound 2 exists as a dimer, where the unsubstituted ring nitrogen atom coordinated intermolecularly to the other stannylene center.
Keywords: Deprotonation; Imidazole; Macrocycle; Sn-II cation; stannylene

Bronsted acid-promoted cyclodimerization of α,β-unsaturated γ-ketoesters: construction of fused pyrano-ketal-lactones and γ-ylidene-butenolides - Vinodkumar, Ramavath; Nakate, Ashwini K.; Sharma, Himanshu; Vanka, Kumar; Rama Krishna, Gamidi; Kontham, Ravindar (ACS Omega, 2024)
Unprecedented MsOH-promoted diastereoselective cascade dimerization and intramolecular lactonization of readily accessible alpha,beta-unsaturated gamma-ketoesters are presented. The results obtained in this work, control experiments, and density functional theory (DFT) calculations suggested that the initial enolization and E to Z isomerization/equilibration of olefin (C=C) of substrate alpha,beta-unsaturated gamma-ketoesters give a Z-isomer preferentially over an E-isomer. Subsequently, the Z-isomer undergoes intermolecular annulation with alpha,beta-unsaturated gamma-ketoesters via domino Michael addition/ketalization/lactonization steps to furnish fused tetracyclic pyrano-ketal-lactone. However, the Z-isomer prefers intramolecular trans-esterification in a competing pathway and gives bicyclic gamma-ylidene-butenolide. The key features of this work include simple Br & oslash;nsted acid catalysis, the formation of three bonds, two rings, and three contiguous stereogenic centers in a single step, DFT calculations, and the assignment of relative stereochemistry through X-ray diffraction (XRD) and two-dimensional (2D) nuclear magnetic resonance (NMR) analyses.

Brønsted acid- and Ni(ii)-catalyzed C-H oxidation/rearrangement of cyclotriveratrylenes (CTVs) to cyclic and acyclic quinones as potential anti-cancer agents - Darole, Ratanamala S.; Choudhary, Shailendra Singh; Sharma, Himanshu; Mali, Bhupendra P.; Gopu, Booblan; Vanka, Kumar; Senthilkumar, Beeran (Organic and biomolecular chemistry, 2024)
This paper describes a simple and practical protocol for the direct synthesis of acyclic and cyclic quinone derivatives via an acid-promoted nickel(ii)-catalyzed inner rim C-H oxidation of cyclotriveratrylene (CTV) and its analogues. The cyclic quinone derivatives resulted from trimethoxy-cyclotriveratrylene (TCTV) through C-C bond formation via intramolecular ipso substitution followed by subsequent anionic rearrangement containing stereo-vicinal quaternary centers. The DFT calculations strongly support the experimental findings and reveal the role of Bronsted acids in the C-H bond activation of CTV. All the newly synthesized compounds were screened for their in vitro anti-cancer activity using colorimetric SRB assay analysis. Among them, compounds 3a, 3d, 3h, 4a, 4b, 4c and 4e exhibited moderate anticancer activity against A549, HCT-116, PC-3, MDA-MB-231, HEK-293 and SW620 human cancer cell lines.

Crystal engineering for intramolecular π-π stacking: effect of substitution of electron-donating and electron-withdrawing groups on the molecular geometry in conformationally flexible Sulfoesters and sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Dabke, Niteen B.; Dash, Soumya R.; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2024)
A series of 21 sulfoester and sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of the presence of either electron-donating (ED) or electron-withdrawing (EW) groups on the intramolecular pi-stacking assembly. The positioning of ED or EW moieties was carried out directly on one of the aromatic rings linked to the sulfonyl or sulfonamide moieties. In contrast, the other aromatic ring (phenyl or pyridine) was connected by a -CH2-CH2- spacer with the sulfonyl or sulfonamide moiety. The purpose of having an ethyl spacer between the two aromatic rings was to achieve conformational flexibility, facilitating the intramolecular pi-stacking assembly between the two aromatic rings. The use of sulfoester/sulfonamide groups allowed more conformational flexibility to attain desired orientations in solids with the interplay of the hydrogen-bonding interactions. Between the two functional groups, sulfonamides offered a more hydrogen-rich environment due to the amine moiety and may exhibit higher H-bonding propensity than the sulfoester moiety. The central idea here was to study the interplay between the hydrogen-bonding and pi & ctdot;pi interactions. The substituent groups chosen were categorized as strong electron-withdrawing (-CF3 and -CN), weak electron-withdrawing (-Cl and -Br), neutral (-H), and good electron-donating (-CH3 and -OCH3) groups. Crystal structure analysis revealed the syn conformation for all the derivatives, enabling intramolecular pi & ctdot;pi interactions between the two aromatic rings, whereas in the sulfonamide derivatives, the molecule takes either midway or anti conformations, except for one pyridine sulfonamide derivative, which showed the syn orientation but lacked intramolecular pi-stacking interactions. The absence of any conventional H-bond forming functional groups in the sulfoester derivatives may have resulted in the syn geometry facilitated by intramolecular pi-stacking interactions. Conversely, H-bond-forming functional groups in the sulfonamide derivatives could have prevented the syn conformation. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed the higher stability of the syn conformation over the midway and anti orientations. The placing of electron-withdrawing and electron-donating groups at the para position of the benzene revealed sulfoesters preferably adopts a syn geometry facilitating the intramolecular pi-stacking, but sulphonamides takes midway or anti-geometry.

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung

Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene

Effect of position of donor units and alkyl groups on dye-sensitized solar cell device performance: indoline-aniline donor-based visible light active unsymmetrical squaraine dyes - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Om., 2024)
Indoline (In) and aniline (An) donor-based visible light active unsymmetrical squaraine (SQ) dyes were synthesized for dye-sensitized solar cells (DSSCs), where the position of An and In units was changed with respect to the anchoring group (carboxylic acid) to have In-SQ-An-CO2H and An-SQ-In-CO2H sensitizers, AS1-AS5. Linear or branched alkyl groups were functionalized with the N atom of either In or An units to control the aggregation of the dyes on TiO2. AS1-AS5 exhibit an isomeric pi-framework where the squaric acid unit is placed in the middle, where AS2 and AS5 dyes possess the anchoring group connected with the An donor, and AS1, AS3, and AS4 dyes having the anchoring group connected with the In donor. Hence, the conjugation between the middle squaric acid acceptor unit and the anchoring -CO2H group is short for AS2, AS5, and AK2 and longer for AS1, AS3, and AS4 dyes. AS dyes showed absorption between 501 and 535 nm with extinction coefficients of 1.46-1.61 x 10(5) M-1 cm(-1). Further, the isomeric pi-framework of An-SQ-In-CO2H and In-SQ-An-CO2H exhibited by means of changing the position of In and An units a bathochromic shift in the absorption properties of AS2 and AS5 compared to the AS1, AS3, and AS4 dyes. The DSSC device fabricated with the dyes contains short acceptor-anchoring group distance (AS2 and AS5) showed high photovoltaic performances compared to the dyes having longer distance (AS1, AS3, and AS4) with the iodolyte (I-/I-3(-)) electrolyte. DSSC device efficiencies of 5.49, 6.34, 6.16, and 5.57% have been achieved for AS1, AS2, AS3, and AS4 dyes, respectively; without chenodeoxycholic acid (CDCA), small changes have been observed in the device performance of the AS dyes with CDCA. Significant changes have been noted in the DSSC parameters (open-circuit voltage V-OC, short-circuit current J(SC), fill factor ff, and efficiency eta) for the AS5 dye while sensitized with CDCA and showed highest DSSC efficiency of 8.01% in the AS dye series. This study revealed the potential of shorter SQ acceptor-anchoring group distance over the longer one and the importance of alkyl groups on the overall DSSC device performance for the unsymmetrical squaraine dyes.

Exploring unconventional σ-hole interactions: computational insights into the interaction of XeO3 with non-aromatic coordinating solvents - Dash, Soumya Ranjan; Vanka, Kumar (Chemphyschem, 2024)
In order to control the explosiveness and shock sensitivity of XeO3, we have investigated its plausible interaction with various non-aromatic coordinating solvents, serving as potential Lewis base donors, through density functional theory (DFT) calculations. Out of twenty six such solvents, the top ten were thus identified and then thoroughly examined by employing various computational tools such as the mapping of the electrostatic potential surface (MESP), Wiberg bond indices (WBIs), non-covalent interaction (NCI) plots, Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, and the energy decomposition analysis (EDA). The amphoteric nature of XeO3 was also explored by investigating the extent of back donation from the lone pair of Xe to the antibonding orbital of the donating atom/group of the solvent molecules. The C-H & mldr;O interactions were also found to be a contributing factor in the stabilization of these adducts. Although these aerogen-bonding interactions were found to be predominantly electrostatic, significant contributions from the orbital contributions, as well as dispersion interactions, were observed. The top three non-aromatic solvents (among the twenty six studied) which form the strongest adducts with XeO3 are proposed to be hexamethylphosphoramide (HMPA), N,N `-dimethylpropyleneurea (DMPU) and tetramethylethylenediamine (TMEDA).
Keywords: Aerogen bonding; Non-Aromatic Solvents; non-covalent interactions; Sigma-hole; XeO3

Far-red active unsymmetrical squaraine dyes containing N-arylated indoline donors for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Jayaraj, Nithyanandhan (Photochemistry and Photobiology, 2024)
Squaraine dyes possess sharp far-red active transition with high extinction coefficient and form aggregates on TiO2 surface. Aggregation of dyes on TiO2 has been considered as a detrimental factor for DSSC device performance, which can be controlled by appending alkyl groups to the dye structures. Hence by integrating alkylated (alkyl groups with both in-plane and out-of-plane) aryl group with indoline moiety to make it compatible with other electrolytes and for controlling the dye-aggregation, a series of squaraine acceptor-based dyes SQA4-6 have been designed and synthesized. SQA4-6 dyes showed absorption between 642 and 653 nm (lambda max), photophysical and electrochemical studies indicated that the HOMO energy levels of this sets of dyes are well aligned with the potentials of I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$ and [Co(bpy)3]2+/3+ redox shuttles for better dye regeneration process. DSSC device efficiency of 3% has been achieved for SQA5 dye with iodolyte (I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$) electrolyte in the presence of 0.3 mM of chenodeoxycholic acid (CDCA). The IPCE profile of DSSC device fabricated with SQA4-6 dyes indicated the contribution of aggregated structures for the photocurrent generation. Dye-sensitized solar cell (DSSC) device efficiency of 3% (Jsc 5.72 mA cm-2, Voc 662 mV and ff 79%) has been achieved for an unsymmetrical squaraine dye, SQA5 with iodolyte electrolyte and the incident photon to current efficiency (IPCE) profile indicates the contribution of aggregated structures for the photocurrent generation.*image
Keywords: aggregation of dye; arylation on N-atom of indoline donor; dye-sensitized solar cell; squaraine dye

In silico discovery of a neutral 2π aromatic silicon aluminum compound - Sharma, Himanshu; Vanka, Kumar (Organometallics, 2024)
The recently developed ab initio nanoreactor (AINR) approach to identifying reaction intermediates and pathways without the necessity of experimental input has been employed in the current work to locate new cyclic silicon-based structures that have the potential to display aromaticity. Using this approach, we have identified many cyclic silicon-based molecules that have been experimentally reported over the past three decades. More importantly, the current work showcases an interesting new molecule that has been discovered through this approach: a four-membered cyclic compound of silicon and aluminum that displays significant 2 pi aromaticity and is capable of the activation of important small molecules such as ammonia.

Iron-catalyzed (E)-selective hydrosilylation of alkynes: scope and mechanistic insights - Sen, Anirban; Tewari, Tanuja; Kumar, Rohit; Vinod, C. P.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Catalysis Science and Technology, 2024)
Iron-catalyzed hydrosilylation of internal alkynes has been rarely reported. Even in these rare cases, additives have been used for the success of the reaction, which often creates a problem for the functional group tolerance of the reaction. Herein, we report an additive-free iron-catalyzed (E)-selective hydrosilylation of internal alkynes in the presence of a phosphine ligand. A low-valent Fe(0) complex [Fe(CO)(3)(BDA)] {[Fe-1]} catalyzed the hydrosilylation of alkynes at 60 to 120 degrees C, exhibited a broad substrate (24 substrates) scope and tolerated different functional groups. The synthetic utility of the reaction was demonstrated by a gram scale experiment, preparing alkenes, and by chemo-selective hydrosilylation. The modus operandi of the reaction has been investigated by i) homogeneity test, ii) radical trapping experiments, iii) X-ray photoelectron spectroscopy, and iv) by preparing a Fe(II) complex as catalyst control. These mechanistic investigations revealed a two-electron pathway for the hydrosilylation of alkynes. In addition, kinetic investigations were undertaken to shed light on the rates of the reaction. Kinetic studies suggest the absence of an induction period, and the reaction is first order with respect to the concentration of iron catalyst [Fe-1] and zeroth order with respect to the substrate (alkyne). The Hammett plot suggests that strongly electron-withdrawing groups on the alkyne favour the hydrosilylation reaction. Meanwhile Eyring analysis suggests that the rate-determining step likely involves an associative pathway. Based on the findings of the mechanistic and kinetic investigation, a plausible Chalk-Harrod-type mechanism is likely to be operative. The proposed mechanism is substantiated by computational investigations, which suggested that the Chalk-Harrod mechanism is kinetically more favored by 15.8 kcal mol(-1) over the modified Chalk-Harrod mechanism.

Lanthanide mimicking by magnesium for oxazolidinone synthesis - Kumar, Rohit; Mahata, Biplab; Gayathridevi, S.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Chemistry- a european journal, 2024)
In the last decade, magnesium complexes have emerged as a viable alternative to transition-metal catalysts for the hydrofunctionalization of unsaturated bonds. However, their potential for advanced catalytic reactions has not been thoroughly investigated. To address this gap, we have developed a novel magnesium amide compound (3) using a PNP framework that is both bulky and flexible. Our research demonstrates that compound 3 can effectively catalyze the synthesis of biologically significant oxazolidinone derivatives. This synthesis involves a tandem reaction of hydroalkoxylation and cyclohydroamination of isocyanate using propargyl alcohol. Furthermore, we conducted comprehensive theoretical calculations to gain insights into the reaction mechanism. It is important to note that these types of transformations have not been reported for magnesium and would significantly enhance the catalytic portfolio of the 7th most abundant element. A monomeric magnesium compound was employed as a catalyst for the cascade cyclization of propargylic alcohol and isocyanate, resulting in the formation of pharmaceutically significant oxazolidinone derivatives. This transformation, previously attributed solely to transition metals or lanthanides, signifies a noteworthy advancement.image
Keywords: catalysis; Magnesium; oxazolidinone; pincer ligand; Sustainability

Nickel-catalyzed tandem conversion of paraformaldehyde : methanol to hydrogen and formate/chemo- and stereoselective hydrogenation of alkynes under neutral conditions - Subaramanian, Murugan; Padhy, Subarna Sukanya; Gouda, Chandrakanth; Das, Tamal; Vanka, Kumar; Balaraman, Ekambaram (Catalysis Science and Technology, 2024)
The development of new catalytic protocols for clean and COx-free hydrogen generation from fundamental feedstocks is always interesting and challenging. Herein, we disclose nickel-catalyzed dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free and activator-free conditions. The dihydrogen generation from this redox combination under neutral, oxidative coupling conditions has been integrated with the hydrogen transfer reactions such as chemo- and stereoselective hydrogenation of alkynes in a tandem manner. This unprecedented strategy provides diverse highly stereoselective olefins with excellent tolerance of reducible functional groups such as ether, silyl ether, aldehyde, keto, ester, nitrile, halides including bromo and iodo groups, and heteroarenes. Additionally, we demonstrated catalytic stereo-interconversion of alkenes under benign conditions. The affordable gram-scale synthesis of some important pharmaceutical bioactive molecules has further enhanced their synthetic value. A tandem dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free conditions followed by semihydrogenation of alkynes is reported.

Rational monomer design for the synthesis of conjugated polymers by direct heteroarylation polymerization - Kakde, Navnath R.; Sharma, Himanshu; Dalvi, Nitin V.; Vanka, Kumar; Asha, S. K (ACS Polymers Au, 2024)
This study focuses on the design concepts that contribute to the C–H activation in bithiophene-flanked monomers incorporating naphthalene diimide (NDI), perylene diimide (PDI), and fluorene (FLU) and their polymerization by direct heteroarylation. Density functional theory (DFT) calculations reveal distinct energy requirements for C–H bond abstraction, which is dictated by the electron-withdrawing strength of the central aromatic core flanked by bithiophene. These provide insights into the reactivity of each monomer for C–H bond activation. Proton NMR spectroscopic experimental results confirm the favorable energetic profiles predicted by DFT, with NDI- and PDI-flanked monomers exhibiting lower energy requirements than fluorene-flanked monomers. Successful polymer synthesis is demonstrated for NDI and PDI, while the fluorene-flanked monomer shows challenges due to its higher energy demands.

Role of aromatic alcohol additives on asymmetric organocatalysis reactions: insights from theory - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-an asian jounrnal, 2024)
The presence of an aromatic additive has been seen to enhance, often significantly, the enantioselectivity and yield in asymmetric organocatalysis. Considering their success across a dizzying range of organocatalysts and organic transformations, it would seem unlikely that a common principle exists for their functioning. However, the current investigations with DFT suggest a general principle: the phenolic additive sandwiches itself, through hydrogen bonding and pi & sdot;& sdot;& sdot;pi stacking, between the organocatalyst coordinated electrophile and nucleophile. This is seen for a wide range of experimentally reported systems. That such complex formation leads to enhanced stereoselectivity is then demonstrated for two cases: the cinchona alkaloid complex (BzCPD), catalysing thiocyanation (2-naphthol additive employed), as well as for L-pipecolicacid catalysing the asymmetric nitroaldol reaction with a range of nitro-substituted phenol additives. These findings, indicating that dual catalysis takes place when phenolic additives are employed, are likely to have a significant impact on the field of asymmetric organocatalysis. The current DFT based study, on a wide range of organocatalysis systems, reveals a general principle by which phenolic additives influence asymmetric organocatalysis reactions. It is shown that the phenolic additive forms a sandwich complex, through hydrogen bonding and pi & sdot;& sdot;& sdot;pi stacking interactions, with the organocatalyst coordinated electrophile and nucleophile, and enhances the enantioselectivity of the system as a result. image
Keywords: Additive; Asymmetric Organocatalysis; Cinchona Alkaloid; Density functional theory; Enantioselective Thiocyanation

Size matters: computational insights into the crowning of noble gas trioxides - Dash, Soumya Ranjan; Sharma, Himanshu; Tiwari, Mrityunjay K.; Greb, Lutz; Vanka, Kumar (Inorganic Chemistry, 2024)
In pursuit of enhancing the stability of the highly explosive and shock-sensitive compound XeO3, we performed quantum chemical calculations to investigate its possible complexation with electron-rich crown ethers, including 9-crown-3, 12-crown-4, 15-crown-5, 18-crown-6, and 21-crown-7, as well as their thio analogues. Furthermore, we expanded our study to other noble gas trioxides (NgO(3)), namely, KrO3 and ArO3. The basis set superposition error (BSSE) corrected interaction energies for these adducts range from -13.0 kcal/mol to -48.2 kcal/mol, which is notably high for sigma-hole-mediated noncovalent interactions. The formation of these adducts was observed to be more favorable with the increase in the ring size of the crowns and less favorable while going from XeO3 to ArO3. A comprehensive analysis by various computational tools such as the mapping of the electrostatic potential (ESP), Wiberg bond indices (WBIs), Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, noncovalent interaction (NCI) plots, and energy decomposition analysis (EDA) revealed that the C-H center dot center dot center dot O interactions, as well as dispersion interactions, play a pivotal role in stabilizing adducts involving larger crowns. A noteworthy outcome of our study is the revelation of a coordination number of 9 for xenon in the complex formed between XeO3 and the thio analogue of 18-crown-6, which is higher than the largest number reported to date.

Taming XeO3 with aza-crowns: computational studies into σ-hole mediated host-guest interactions - Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2024)
Various aza-crowns with different sizes and substituents have been explored computationally as potential hosts for stabilizing the explosive guest xenon trioxide (XeO3) through sigma-hole-mediated aerogen bonding interactions. Interestingly, aza-crowns demonstrate superior binding towards XeO3 compared to their oxygen and thio counterparts. However, unlike the latter cases, where the binding was found to be increasingly favorable with the increase in the size of the crowns, aza-crowns exhibit a variable size preference for XeO3, peaking with aza-15-crown-5, and reducing thereafter with increase in crown size.
Keywords: aza-crowns; host-guest systems; noncovalent interactions; sigma (sigma) hole; Xenon

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Uncovering diverse reactivity of NHCs withdiazoalkane: C-H activation, C=C bond formation,and access to N-heterocyclic methylenehydrazine - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Science, 2024)
N-heterocyclic carbenes (NHCs) have attracted significant attention due to their strong sigma-donating capabilities, as well as their transition-metal-like reactivity towards small molecules. However, their interaction with diazoalkanes remains understudied. In this manuscript, we explore the reactivity of a series of stable carbenes, encompassing a wide range of electronic properties, with Me3SiCHN2. 5-SIPr activates the C-H bond of Me3SiCHN2, resulting in the formation of a novel diazo derivative (1), while carbenes such as 5-IPr, 6-SIPr, and diamido carbene yield N-heterocyclic methylenehydrazine derivatives (3, 4, and 8). The reaction of Me3SiCHN2 with 5-ItBu unexpectedly leads to the formation of a triazole ring linked with the imidazole moiety via a CC double bond (6) alongside the azine product (7). Substituting the diazoalkane with diazoester consistently yields azine derivatives (9-12 and 14). Only in the case of 5-ItBu, an imidazolium salt with tetrazenide anion (13) was obtained as a side product. The reaction of 4 with HCl resulted in the desilylprotonation to form a salt, 5a, which undergoes deprotonation upon using bases such as Et3N and KHMDS to form N-heterocyclic methylene hydrazine, 5. Theoretical calculations have been conducted to elucidate the diverse mechanisms underlying product formation.

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Unravelling polymorphism-driven luminescence in GFP chromophore analogues: insights into the phase transition and morphology-dependent optical waveguide properties - Dabke, Niteen B.; Raut, Yash; Mali, Bhupendra P.; Pandya, Rinu; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Journal of Materials Chemistry C, 2024)
The advent of multi-emission organic solid-state materials in response to external stimuli has sparked the scientific community due to their potential application in developing sophisticated optoelectronic sensors and bioanalytical tools. This article presents green fluorescent protein chromophore (GFPc) analogue-based polymorphs exhibiting significantly different emissions due to various noncovalent interactions in the supramolecular environment and conformational alterations in the crystalline state. In both compounds (A and B), the polymorphs undergo monotropic thermal phase transitions that are characterized by DSC, HSM, and VT-PXRD techniques. The distinct fluorescent emission characteristics of these polymorphs demonstrated morphology-related optical waveguiding features. Specifically, the plate-type Form A1 emitted light with a 2D blue hue, while the needle-type Form A2 emitted light with a yellowish-green colour. Additionally, the impressive waveguiding capabilities of Form B1 were explored in both straight and singly/doubly bending configurations to facilitate fluorescence propagation. Consequently, there is significant interest in developing organic materials based on GFP chromophores, which exhibit low emission in solution but display multi-fluorescent emission in the solid state. These materials are promising for applications such as optoelectronic devices, security tags, live cell imaging, and fluorescent inks. Polymorphs of GFPc analogs A and B display differences in their optical waveguiding properties in 1D and 2D depending on the crystal shapes. Furthermore, Form B1 demonstrates efficient optical waveguiding capabilities even when the crystal is bent.

Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors

Unveiling the inverse sandwich complexes of XeO3: a computational exploration - Dash, Soumya Ranjan; Vanka, Kumar (Inorganic Chemistry, 2024)
Our study introduces the design of inverse sandwich (iSw) complexes incorporating a noble gas compound: xenon trioxide (XeO3). Through comprehensive computational analyses, we have investigated the critical factors influencing their stability by employing a variety of state-of-the-art computational tools. We demonstrated that the coordination number of xenon in the iSw complex of XeO3 with 18-crown-6 is influenced by the presence of a rare, weakly stabilizing XeXe interaction between the XeO3 molecules. Furthermore, we observed that the stability of iSw complexes of 1,3,5-triphenylbenzene (TPB) and its derivatives is not solely attributed to aerogen bonding, but also involves contributions from C-HO interactions and back-donation from the lone pair of Xe to the antibonding C-C orbitals of TPB. Additionally, the significant contributions from orbital interactions and dispersion interactions in the TPB derivatives highlight the multifaceted amphoteric properties of XeO3 and reveal that the iSw complexes of TPB and derivatives are not predominantly governed by electrostatic interactions, contrary to conventional belief.

Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes

Bioinspired synthesis of bridged isochromane fused pyrazoles by a silver catalyzed cascade reaction and its application for antibacterial activity - Singh, Bhuvnesh; Tewari, Shreya; Kaur, Manleen; Sharma, Himanshu; Vanka, Kumar; Singh, Neetu; Singh, Ravi P. (JACS Au, 2025)
A stereoselective silver catalyzed one pot vinylogous aldol addition followed by a cascade [4+2] cycloaddition reaction of α-arylidene pyrazolinones to in situ generated isochromenylium ions has been developed, which provides an unprecedented bridged [2.2.2] [3.3.1] pentacyclic [5-6-6-6-6] skeleton consisting of an isochroman, chroman, and a pyrazole unit in one molecule with good to high yields as a single diastereomer. This method offers mild reaction conditions, wide substrate compatibility, excellent scalability and easy derivatization. A DFT study was carried out to clarify the reaction mechanism. It was exciting to observe that the unprecedented bridged isochromans synthesized here have shown excellent selectivity toward Gram-positive and Gram-negative bacteria. We demonstrate that while some structures are broad spectrum antibacterial there are two distinct structures that can be explored for selective activity.
Keywords: Antibacterial; Bridged [2.2.2] [3.3.1]; ROS; Stereoselective; Vinylogous aldol addition; [4+2] cycloaddition

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides

Cocrystals of the green fluorescence protein chromophore analogue: coformer-induced switch between AIE and ACQ - Suresh, Sneha; Dabke, Niteen B.; Pandya, Rinu; Vanka, Kumar; Dutta, Madhusudan; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Fluorescent organic solids hold great potential for advancing photonics applications. However, tuning their solid-state photoluminescent emissions remains a significant challenge. In this study, we report the synthesis and characterization of five cocrystals (two cocrystal polymorphs) derived from a pristine imidazolinone derivative (A) and the various coformer molecules, namely 1,2,4,5-tetrafluoro-3,6-diiodobenzene, 1,2,4,5-tetrafluoro-3,6-dibromobenzene, perfluoronaphthalene, and 3,4,5-trifluorobenzoic acid. The structural and optical properties of these cocrystals were examined by using single-crystal X-ray diffraction, absorption spectroscopy, photoluminescence spectroscopy, and photoluminescence decay spectroscopy. Cocrystals I, II, and III are isomorphous pairs and exhibit three-dimensional isostructurality, where the coformer molecules bridge adjacent helices of compound A, leading to aggregation-induced emission. In contrast, the cocrystal polymorphs IVA and IVB developed using coformer 3,4,5-trifluorobenzoic acid form two-dimensional sheet-like structures mediated by pi-stacking interactions between the coformers and molecule A, with interplanar distances ranging from 3.2 to 3.5 & Aring;. These stronger pi-pi interactions promote nonradiative decay pathways, resulting in reduced or quenched fluorescence and an aggregation-caused quenching effect. To gain further insights into their electronic properties, theoretical analysis including frontier molecular orbitals, time-dependent density functional theory, Hirshfeld surface analysis, molecular electrostatic potential, and noncovalent interaction plots were performed.

The critical helping hand of water: theory shows the way to obtain elusive, granular information about kinetic asymmetry driven systems - Bajpai, Priyam; Thulasiram, Shrivatsa; Vanka, Kumar (Chemical Science, 2025)
Kinetic asymmetry is crucial in chemical systems where the selective synthesis of one product over another, or the acceleration of specific reaction(s) is necessary. However, obtaining precise information with current experimental methods about the behavior of such systems as a function of time, substrate concentration and other relevant factors, is not possible. Computational chemistry provides a powerful means to address this problem. The current study unveils a two-pronged computational approach: (i) full quantum chemical studies with density functional theory (DFT), followed by (ii) stochastic simulations with a validated Gillespie algorithm (GA) (using representative model systems where necessary), to study the behavior of a kinetic asymmetry driven unidirectional molecular motor (1-phenylpyrrole2,2 `-dicarboxylic acid) (Nature, 2022, 604 (7904), 80-85). Our approach allows us to understand what is really taking place in the system, underlining the crucial role played by water molecules in facilitating the rotation of the motor. It is seen that water lubricates the motion by increasing the rotation rate constant of the final step by, remarkably, more than ten orders of magnitude! These insights further serve to explain the efficient rotation of the very recently reported gel-embedded molecular motor (Nature, 2025, 637 (8046), 594-600), providing an upper limit for the allowed rotation barrier in such systems, and thus also casts light into the functioning of bio-molecular motors. The current work therefore provides a template for carefully and properly studying a wide variety of important, kinetic asymmetry driven systems in the future.

Depolymerization of waste polycarbonates to value-added products - Padhi, Ganeshdev; Pansare, Vaibhav Ramachandra; Bajpai, Priyam; Krishna, Gamidi Rama; Vanka, Kumar; Barsu, Nagaraju (ChemSusChem, 2025)
Additive free aminolysis method developed for the depolymerization/upcycling of polycarbonates. We report here chemical recycling of polycarbonate under ambient conditions to get its monomer bisphenol A, monoaminocarbamate and biscarbamates in 1 : 2 : 1 ratio respectively. By employing the secondary amine as the aminating reagent, facilitates the depolymerization to work under additive/catalyst free conditions. The developed method deals with depolymerization of waste polycarbonates and works even with late-stage amine derivatives such as amoxapine and desloratadine which are drugs molecules known to treat neurotic disorders and allergies respectively. The reaction can be scaled up and works with similar efficacy which depicts the efficiency of the depolymerization of wasteend-of-life polycarbonate plastic waste. The biscarbamate and bisphenol-A was further subjected for the post functionalization to obtain amides and phenol in good yields. Developed additive/catalyst free aminolysis of waste polycarbonates to carbamates and monomer BPA at ambient conditions. Variety of secondary amines were screened including the late stage amine derivatives like amoxapine and desloratadine which delivered the expected products successfully. Later the developed methodology was even applied for the different end-of-life polycarbonates with the secondary amine and achieved the depolymerization without any obstacle. Further carried out the scale up reaction and derivatization of carbamates and BPA to amide and phenol synthesis. image
Keywords: Aminolysis; carbamates; depolymerization; End-of-life; Polycarbonate

Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

From Delocalization to Disruption: The Role of Aromaticity in N-Heterocyclic Carbenes' Reactions with Diazoalkane and Diazoester - Sharma, Himanshu; Fernandez, Israel; Vanka, Kumar (Journal of Organic Chemistry, 2025)
Aromaticity is a fundamental force shaping molecular stability and reactivity, yet its dynamic role along reaction coordinates remains poorly understood. In this study, we unveil how dynamic changes in aromatic character govern the reactivity of 5-ItBu with diazoalkanes and diazoesters through a multifaceted computational approach. By integrating electronic, magnetic, structural, and energetic aromaticity descriptors, we demonstrate that the retention of aromaticity along the reaction path markedly lowers activation barriers, while its disruption imposes significant energetic penalties. Activation strain model (ASM) and energy decomposition analysis (EDA) further underscore the role of aromatic stabilization in enhancing orbital interactions that drive reactivity. These insights establish a cohesive mechanistic framework, highlighting aromaticity not merely as a static structural feature but as a tunable lever in the design of selective transformations and next-generation catalysts.

Germylene mediated reductive C-C and C-N coupling of an isocyanide and its device application - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Shinde, Dipak Dattatray; Venugopal, Geethu; Vanka, Kumar; Rath, Arup K.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2025)
We have demonstrated a unique reductive coupling of 4-iodophenyl isocyanide, facilitated by a perimidine-based N-heterocyclic germylene (NHGe), which yields a bis-spirogerma compound featuring simultaneous C-C and C-N bond formation. This reaction, which leads to the oxidation of germanium from +2 to +4, represents a significant departure from previously documented isocyanide-germylene interactions. The product exhibits extensive conjugation across its bicyclic C4Ge2N2 framework, conferring distinct photophysical properties, including prominent orange luminescence in both solution and solid states. The photophysical properties are supported by the TD-DFT calculations confirming an n ->pi* transition. The potential application of this compound in optoelectronic devices, particularly as a hole transport layer in PbS quantum dot solar cells, is also explored, with promising preliminary results.
Keywords: Germylene; hole transport layer; Isocyanide; reductive coupling

Heterolytic cleavage of the B–H bond in H3B·L (L = THF, NMe2H) by an electrophilic Ir(iii) pincer complex [Ir(H)(PMe3)(tBu4POCOP)][BAr F4] - Pradhan, Mitarani; Surati, Zeel Y.; Pal, Apurba Kumar; Vanka, Kumar; Jagirdar, Balaji R. (2025)
<div class="abstract author" id="aep-abstract-id6" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Six- and five-coordinate iridium complexes, [Ir(H)Cl(PMe3)(tBu4POCOP)] (2) (tBu4POCOP = κ3-C6H3-2,6-(OPtBu2)2) and [Ir(H)(PMe3)(tBu4POCOP)][BArF4] (3), respectively, have been synthesized and characterized. The reactivity of the electrophilic 16-electron iridium(III) complex 3 with H2, H3B·THF, H3B·NMe2H, and H3B·NMe3 was investigated. The reaction of complex 3 with H2 resulted in the formation of trans-[Ir(H)(η2-H2)(PMe3)(tBu4POCOP)][BArF4] complex 5. Complex 3 was found to activate the B–H bonds in H3B·THF and H3B·NMe2H (DMAB) in a heterolytic fashion. The reaction of complex 3 with H3B·THF at 298 K afforded trans-[Ir(H)2PMe3(tBu4POCOP)] complex 6 and a boronium compound, [H2B(THF)2][BArF4]. Monitoring the reaction from 179 to 298 K by NMR spectroscopy revealed the formation of a σ-borane intermediate, trans-[Ir(H)(η1-HBH2·THF)PMe3(tBu4POCOP)][BArF4] (3a-Int), en route to the final products observed at 298 K. The formation of this intermediate species was also investigated by density functional theory (DFT) calculations. The reaction of complex 3 with H3B·NMe2H at 298 K yielded a mixture of complexes 3 and 5 and a cyclic diborazane [H2BNMe2]2. The reaction was found to proceed via intermediates, a σ-borane complex, trans-[Ir(H)(η1-HBH2·NMe2H)PMe3(tBu4POCOP)][BArF4] (3b), complex 6, [(NHMe2)2BH2][BArF4], and H2B<img alt="[double bond, length as m-dash]" border="0" src="https://www.rsc.org/images/entities/char_e001.gif" style="border: none; color: rgba(0, 0, 0, 0.79); font-family: "Source Sans Pro", source-sans-pro, museo_sans300, museo-sans, Arial, sans-serif;" />NMe2. Complex 3 exhibited no reactivity with H3B·NMe3.

Hypersilylsilylene-supported Ni(0) toluene and Ni(II) complexes with catalytic application - Ajithkumar, V. S.; Bisai, Milan Kumar; Ghanwat, Pratiksha B.; Raj, K. Vipin; Singh, Geetika; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2025)
The reaction of Ni(COD)2 with [PhC(NtBu)2SiSi(SiMe3)3] (1) in toluene results in the formation of an 18-electron silylene-Ni(0) toluene complex (2). The analogous reaction with 1,3-DFB instead of toluene affords the C-H activation followed by ring walking leading to the allylic cyclooctene adduct, the (eta 3-C8H13)Ni(II) complex (3). DFT calculations were carried out to elucidate the mechanism as well as to gain insight into why 1,3-DFB undergoes C-H bond activation instead of C-F bond activation. The use of NiCl2DME permits access to 16-electron (tetrylene)2NiCl2 (Si(4) and Ge(5)) species, and 4 was later used as a catalyst for the C-N coupling reaction.

Investigating the visible range photoresponse of an organic single-crystal analogue of the green fluorescent protein - Virole, Vishal; Dabke, Niteen; Verma, Sahil; Kumar, Ajay; Pandya, Rinu; Husale, Sudhir; Vanka, Kumar; Gonnade, Rajesh; Kanawade, Rajesh (Nanoscale, 2025)
The growing demand for lightweight, flexible, semi-transparent and low-cost photodetectors (PDs) in wearable electronics and optical communication systems has prompted studies to investigate organic materials as feasible alternatives to conventional inorganic PDs. However, modern organic PDs often face responsivity, detectivity, and photoresponse speed limitations, particularly in the visible range. Here, we present the photoresponse of an organic single-crystal analogue of the green fluorescent protein (GFP) chromophore photodetector, fabricated on a silicon nitride substrate. A significant increase in photocurrent was detected upon illumination with visible wavelengths (532 nm, 630 nm, and halogen light). A remarkably consistent and repeatable photoresponse was obtained during the ON and OFF illumination cycles. The device showed the dependence of photocurrent on the applied bias voltages. The measured photocurrent, responsivity, detectivity, rise time, decay time, noise equivalent power and external quantum efficiency are studied for different wavelengths. Strikingly, the fabricated device demonstrates excellent performance in the visible region compared to several conventional organic and inorganic PDs. The observed responsivity and detectivity values for the device are 98 mA W-1 and 7.94 x 108 Jones, respectively. Furthermore, the device also exhibits rapid photoresponse dynamics with a rise time of 180 ms and a decay time of 152 ms. The excellent photodetection features indicate that the single crystal GFP could serve as a versatile broadband material for future applications in optoelectronics.

Iron-catalyzed chemoselective reduction of enimines to N-Allylic amines via hydrosilylation - Tewari, Tanuja; Shaikh, Maulali H.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2025)
Chemoselective hydrosilylation of unsaturated imines is challenging as the two double bonds compete for the reaction. Here in, we report an iron-catalyzed chemoselective hydrosilylation of enimines leading to the generation of allyl amines in the presence of phosphine ligand. A low-valent Fe(0) complex [(BDA)Fe(CO)3] catalyzed the hydrosilylation of enimine at room temperature and exhibited broad substrate scope including a variety of enimine (cinnamylimine, allylimine) and ketimine. Mechanistic investigations revealed that the reaction proceeds through an oxidative addition of the silane compound, leading to the formation of an iron hydride intermediate. Subsequently, a two-electron pathway facilitates the hydrosilylation of the enimine substrate. This has been supported by preparing a well-defined Fe(II)-silane complex and using it as a catalyst control. Based on experimental and computational investigations, a plausible Chalk-Harrod-type mechanism is proposed.
Keywords: Cinnamyl amine; Imine hydrosilylation; iron catalysis; Iron hydride; Phosphine

Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.

Manganese(i)-catalyzed dehydrogenative borylation of terminal alkynes - Ghanwat, Pratiksha B.; Bora, Debashree; Pandya, Rinu; Vanka, Kumar; Saha, Biswajit; Sen, Sakya S. (Dalton Transactions, 2025)
Compounds containing carbon-boron bonds serve as valuable intermediates for constructing more complex molecules by transforming these bonds into other carbon-element bonds. The catalytic dehydrogenative borylation of carbon-hydrogen bonds using HBpin presents an appealing method for synthesizing carbon-boron bonds. While this approach has been extensively explored with noble metals for various types of carbon-hydrogen bonds, its application with manganese-based catalysts remains rare. This study explores a dehydrogenative borylation process employing an Earth-abundant transition metal catalyst, FcbpyMn(CO)3Br (Mn(i)), in combination with HBpin under mild conditions. Arylalkynes featuring electron-withdrawing, electron-donating, and heteroaryl substituents yielded good to excellent results. Thorough DFT calculations were performed to understand the mechanism.

Pair of dinuclear Fe(II) enantiomers: syntheses and structures of ΛΔ/ΔΛ-Bis(Dihydridoborate) complexes - Kaur, Urminder; Gayen, Sourav; Sharma, Himanshu; Vanka, Kumar; Ghosh, Sundargopal (CHEMISTRY-A EUROPEAN JOURNAL, 2025)
In our effort to establish a direct synthetic approach for bis(dihydridoborate) complexes of first-row transition metals, we have investigated the reactivity of [Cp*Fe(dppe)Cl] (dppe =1,2-bis(diphenylphosphino)ethane) with Na[BH3L] (L =2-mercaptopyridine (mp) and 2-mercaptobenzothiazole (mbz)) that led to the formation of iron(II) dihydridoborate complexes, [Cp*Fe{kappa 3-S,H,H-(H2BH(L))}] 1 a-b (L=mp (1 a) and L=mbz (1 b)). Further, in an attempt to isolate the bis(dihydridoborate) complex of iron by the insertion of borane into the kappa 2-N,S-chelated iron complex, [(dppe)Fe{kappa 2-N,S-(mp)}2] (2), we have isolated and structurally characterized a rare example of dimeric iron bis(dihydridoborate) complex, [Fe{kappa 3-S,H,H-(H2BH(mp))}2]2, Lambda Delta/Delta Lambda-3 as pair of enantiomers. Interestingly, these enantiomers Lambda Delta/Delta Lambda-3 have two trans-[Fe{kappa 3-S,H,H-(H2BH(mp))}2] moieties bridged through sulfur atoms of 2-mercaptopyridinyl ligands, where the iron centres are hepta-coordinated. The natural bond-orbital (NBO) analyses of Lambda Delta-3 and Delta Lambda-3 show considerable electron donation from the filled sigma B-H bonding orbital to vacant dz2 \${{d}_{{z}<\^>{2}}}\$ orbital of iron with a substantial contribution from the hydrogen atoms. The localized orbital bonding analysis (LOBA) method suggests that all the iron centres are in +2 oxidation state.
Keywords: B-H activation; Bis(dihydridoborate); Enantiomer; Heptacoordinate; iron

Palladium(II)-catalyzed desymmetrization of 2-alkynylbenzoate-tethered cyclohexadienones for the synthesis of polycyclic compounds - Rai, Archana; Bajpai, Priyam; Gamidi, Rama Krishna; Vanka, Kumar; Das, Utpal (Organic Letters, 2025)
Pd-catalyzed cascade cyclization of 2-alkynylbenzoate-tethered cyclohexadienone was developed for the single step synthesis of isocoumarin-fused dihydrochromenones. This highly atom economical method proceeds via 6-endo-dig cyclization of tert-butyl benzoate with a tethered alkyne. By modulating the reaction solvent and metal catalyst, the methodology was diverted for the purposeful synthesis of either of the E/Z tetra-substituted alkenes.

Pushing the boundaries of pnictogen-bonding organocatalysis: a clash of Sb(III) versus Bi(III) - Sharma, Jyoti; Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2025)
The sigma-hole-mediated noncovalent organocatalysis involving the pnictogen (Pn) elements has thus far been explored mostly from nitrogen to antimony, with antimony identified as the most effective catalyst. Herein, density functional theory calculations have been carried out to demonstrate that tri-aryl (Ar)-substituted bismuth(III) complexes can outperform their antimony counterparts in both anion (Cl-) binding and catalytic activity. Using a range of computational methods, a good correlation between the sigma-hole strength, chloride binding affinity, and the reaction barrier is established. Notably, the findings reveal that dispersion interactions are the dominant force in catalysts with weaker sigma-holes, while electrostatic interactions prevail in catalysts with stronger sigma-holes (for the anion abstraction step). In all cases, Bi(III) catalysts emerge as the winner over the Sb(III) analogues. Additionally, beyond the primary Pn. . .Cl interactions, several secondary interactions such as Cl. . .H/F-C(Ar) and Cl-. . . H-C(Si-TBS) also play a significant role in stabilizing the transition states.
Keywords: Antimony; Bismuth; organocatalysis; pnictogen; sigma (sigma) holes

Silylene-copper(i) catalysis: regioselective protoboration of terminal alkynes - Kaulage, Sandeep H.; Shah, Brij Kumar; Panday, Rishukumar; Sharma, Himanshu; Vanka, Kumar; Khan, Shabana (Chemical Communications, 2025)
Herein, we report an efficient regioselective protoboration of the terminal alkynes catalyzed by newly synthesized silylene-copper(i)-aryl complexes. This method offers a broad substrate scope, good functional-group compatibility, and a gram-scale synthetic ability. The insight into the mechanistic cycle is also provided with the support of experimental and theoretical studies.

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.

Synthesis, crystal structure, DFT calculation and catalytic activity of a polymer complex of zinc(II) succinate with 2-amino-1,3,4-thiadiazole - Nuralieva, Guzal; Alieva, Mushtariy; Torambetov, Batirbay; Leslee, Denzil Britto Christopher; Senthilkumar, Beeran; Kaur, Simranjeet; Dabke, Niteen B.; Vanka, Kumar; Ashurov, Jamshid; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Journal of Molecular Structure, 2025)
A polymer complex of zinc(II) succinate with a 2-amino-1,3,4-thiadialole ligand, denoted as [Zn2L2(suc)2]n, was synthesized and characterized by NMR, ESI-MS, FTIR, and FT-Raman spectroscopy, TGA, and X-ray crystallography. The polymer complex crystallizes in the orthorhombic noncentrosymmetric Pna21 space group and features a five-coordinate zinc ion in a distorted spherical square pyramidal geometry. The Hirshfeld surface analysis was carried out to evaluate the intermolecular interactions. Additionally, computational studies were also conducted to assess the stability of the Zn polymer complex and analyze the electron density distribution of the HOMO and LUMO. The catalytic activity of our complex was tested, interestingly, that showed good results for Biginelli reactions with distinct substrate scope in good to high yield at mild reaction conditions.
Keywords: DFT; Dihydropyrimidinones; Polymer complex; succinate; Thiadiazole; zinc

Synthesis of diamido N-heterocyclic imines (DAC = NH) via staudinger or reductive N-N bond cleavage approach - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
This report communicates the first examples of N-heterocyclic imines based on electrophilic diamido carbenes (DACs). While 2 is prepared by classical Staudinger synthesis, 4 is obtained via an unusual reductive N-N bond cleavage of an azine by HCl. The exocyclic C=N bond lengths in 2 and 4 are substantially shorter than those based on N-heterocyclic carbenes and cyclic (alkyl)(amino)carbene reflecting the electrophilic character of DACs.

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.

Unlocking thermodynamic enolate for kinetically controlled desymmetrizing vinylogous (4+1) carbospiroannulation - Singh, Sanjay; Singh, Abhijeet; Pandya, Rinu; Vanka, Kumar; Singh, Ravi P. (Chemistry-A European Journal, 2025)
An unprecedented thermodynamically unfavorable (4+1) deysmmetrizing spiroannulation through a thermodynamic enolate intermediate, enabling a single-step synthesis of ubiquitous scaffolds such as all-carbon chiral spirocycles, is disclosed. In this spiroannulation, we present a vinylogous organocatalytic enantioselective desymmetrizing (4+1) cycloaddition approach involving alkylidene malononitrile and cyclopent-1,3-dienone. This carbospiroannulation method produces functionally enriched spiro[4,4]nonane structures with three stereocenters, has presented good-to-high yields and enantiomeric ratios. Detailed DFT calculations reveal an intriguing reaction mechanism, which validates our observations.
Keywords: 3-diones; alkylidene malononitrile; cyclopent-1; quaternary stereocenters; spiro compounds; thermodynamic enolate

Visible-light active π-extended unsymmetrical squaraine dyes for dye-sensitized solar cells: steric effects for controlling the aggregation of dyes - Jadhav, Avinash P.; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
The dye-anchored TiO2 photoanode plays a vital role in the light harvesting and charge separation processes in dye-sensitized solar cells. Aggregation of dyes (H- and J-type) on the TiO2 surface is a facile process due to the presence of a periodical dye anchoring sites on the exposed facet of titania, and such self-assembled dye structures help broadening the absorption profile. However, photocurrent generation from such aggregated structure is a challenging task in dye-sensitized solar cell devices. Hence, controlling the dye aggregation on the TiO2 surface is an important aspect. Controlling the aggregation of dyes by which (i) an enhanced photocurrent generation (J SC) and (ii) enhanced V OC can be achieved by including the steric factors to the dye design principles, the steric factor in the sensitizer may help passivate the TiO2 surface to avoid the charge recombination process between electrons present in TiO2 and the oxidized electrolyte. On the other hand, extension of pi-conjugation in a sensitizer helps enhance the light absorption in the visible region besides modulating the HOMO and LUMO energy levels. Hence, synergizing both pi-extensions along with features that control the dye aggregation has been considered in designing visible active squaraine dyes. A thiophene pi-spacer was inserted in between a visible-light active unsymmetrical squaraine unit and a cyanoacetic acid acceptor unit to provide the AJ1 and AJ2 dyes. Though both the dye molecules possess a similar pi-framework, the AJ2 dye was functionalized with both in-plane and out-of-plane alkyl groups to decrease the aggregation of dyes on the TiO2 surface compared to AJ1. The AJ1 and AJ2 dyes absorbed at 560 nm with shoulder peaks appeared at 528 nm, which can be assigned to vibronic progression (1082 cm-1), and additional characteristic peaks of thiophene appeared at 392 nm with the molar extinction coefficient of 1.16-1.19 x 105 M-1 cm-1 in CH3CN. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of iodolyte (I-/I3 -) electrolyte with sufficient overpotentials for charge injection and dye regeneration processes, respectively. The highest DSSC device efficiency of 7.37% (J SC 14.44 mA/cm2, V OC 0.771 V, ff 67.1%) was achieved for the AJ2 dye with iodolyte (I-/I3 -) electrolyte in the presence of 2 equiv of optically transparent coadsorbent chenodeoxycholic acid (CDCA), which showed a good IPCE response in between 400 and 700 nm. Further, cosensitization of visible-light active AJ1, AJ2, and SQA10 dyes with a complementary far-red active SQS4 dyes showed the device efficiencies of 5.53% (AJ1:SQS4:CDCA), 7.14% (AJ2:SQS4:CDCA), and 7.18% (SQA10:SQS4:CDCA) with a good IPCE response in the 400-720 nm region.
Keywords: cosensitization; Dye aggregation; Dye-sensitized solar cells; pi-extended squaraine dye; visible-lightactivedyes

Auxiliary triazatruxene donor-based squaraine dyes for dye-sensitized solar cells: cis- and trans- configuration of dyes for modulating photophysical and electronic properties - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemistry-an Asian Journal, 2026)
In DSSCs, dye regeneration efficiency and dye aggregation on the TiO2 surface can be modulated by using bulky aromatic donors wrapped with alkyl groups. Introduction of rigid aromatic rings around the donor unit of a dye will directly impact the driving force for electron injection and dye regeneration of a dye. In this work, we designed and synthesized KNS dyes with an auxiliary TAT donor integrated with a visible active squaraine dye. Here, octupolar-structured auxiliary TAT wrapped with alkyl groups is used as a strong donor and shelter to reduce the dye aggregation and charge recombination process. Further, to improve the light-harvesting efficiency and incident photon-to-current conversion efficiency of DSSC devices fabricated with KNS dyes, the central squaric acid unit has been modified by appending the electron-withdrawing dicyano group at the central squaric unit, and the trans-configured KNS1 dye was converted to cis-configured KNS2 dye. The power conversion efficiency of devices based on the KNS dyes was studied with and without 3 equivalents of CDCA by using the I-/I3 - electrolyte. Out of these devices, the KNS1: CDCA (1:3) based cell exhibited the best PCE of 6.25% with V OC of 793 mV, J SC of 11.08 mA cm-2, and ff of 71%.
Keywords: Bulky donor unit; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

Intramolecular alder-ene reaction of 2-methyl-4-(alkynyloxy)cyclohexa-2,5-dienones: catalyst-free access to hydrobenzofuran derivatives - Rai, Archana; Bajpai, Priyam; Kundu, Ananya I.; Vanka, Kumar; Das, Utpal (Organic Letters, 2026)
An atom-economical intramolecular Alder-ene reaction has been developed to construct hydrobenzofurans via the direct coupling of an allylic hydrogen atom to an alkyne. This transformation delivers hydrobenzofuran and hydroindole scaffolds in a single step, incorporating all atoms of the starting materials and exemplifying high atom economy. The synthesized products serve as versatile intermediates and exhibit notable reactivity toward further derivatization, as showcased through a range of transformations enabling rapid access to structurally diverse and complex molecules.

Kekule diradicaloid with a naphthalene spacer - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2026)
The availability of a diverse array of carbenes led to the generation of a catalog of carbene based Kekule diradicaloids, but the linker in such molecules is mostly limited to phenylene or biphenylene. Here we have prepared a closed-shell Kekule diradicaloid (2) separated by a naphthalene moiety and stabilized by two capping 5-SIDipp [5-SIDipp = 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] from the reduction of the corresponding dication (1). The combined experimental and computational studies confirm that 2 is in a closed-shell singlet state exhibiting a singlet-triplet energy difference (Delta ES-T) of 18.7 kcal/mol, which is considerably lower than Thiele's version (29.1 kcal/mol).

Magnesium-ligand cooperation enables regioselective transfer hydrogenation of quinolines to 1,2-dihydroquinolines - Mahata, Biplab; Sharma, Jyoti; Vanka, Kumar; Sen, Sakya S. (Organic Letters, 2026)
We report the first magnesium-catalyzed regioselective reduction of quinolines to 1,2-dihydroquinolines, utilizing H3N & centerdot;BH3. This protocol operates under mild conditions and tolerates a broad range of functional groups. Comprehensive mechanistic investigations, including kinetic analysis, deuterium labeling, and density functional theory calculations, elucidate a concerted hydride transfer pathway. This work serves as a blueprint for employing s-block metals with high-precision reactivity, which are traditionally reserved for transition metals.

NHC-based diazo compounds: pathways to N2 liberation or dimerization - Balayan, Kajal; Tiwari, Prabhakar; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Journal of Organic Chemistry, 2026)
We previously reported the C-H bond cleavage of Me3SiCHN2 by 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene (5-SIPr) to form 1. In this article, we showed that electron-poor diamido carbene 5-tBuDAC also cleaves the C-H bond of Me3SiCHN2 to form 5, unlike its ring-expanded congener 6-DippDAC, which forms N-heterocyclic methylene hydrazine. The divergence of reactivity has been explained with the help of DFT studies. Further divergence occurs when 1 and 5 were reacted with HCl. While dimerization was observed with 5-SIPr based diazoalkane to give quinoidal tetrazine (2), N2 elimination occurs from 5-tBuDAC based diazoalkane to afford 7 and 8. This contrasting behavior highlights the subtle yet profound influence of the N-heterocyclic carbene (NHC) framework on the fate of the diazo units. DFT studies shed light about the mechanism for the formation of 2 as well as reveal that N2 elimination is thermodynamically favored over dimerization for 5.

(NHC-olefin)-nickel(0) nanoparticles: an efficient and selective catalyst for hydrogenation reactions at low temperature and pressure - Avello, Marta G.; Singh, Geetika; Truong-Phuoc, Lai; Vidal, Loic; Papaefthimiou, Vasiliki; Chesse, Matthieu; Gruber, Nathalie; Chetcuti, Michael J.; Vanka, Kumar; Ritleng, Vincent; Pham-Huu, Cuong; Michon, Christophe (Journal of Catalysis, 2026)
The reduction of a NHC-cinnamyl nickel(II) organometallic complex through the use of different MeMgBr or MeMgCl reagents led to two types of NHC-olefin-coordinated nickel nanoparticles. Both of these unsupported nickel-NHC based nanomaterials behaved under hydrogen pressure as effective and selective catalysts operating at low temperature (<= 80 degrees C), pressure (<= 20 bar) and loading (<= 6 mol%) for the reductions of broad scopes of alkenes, alkynes, imines and heterocycles, including a challenging tetra-substituted alkene. Among these two nickel-NHC nanocatalysts, the one generated with MeMgCl showed a significant high catalytic activity with high yields and could stand the comparison with Raney nickel and state-of-the-art nickel nanocatalysts. For example, by studying the hydrogenation of 1-phenylcyclohexene in ethanol at 60 degrees C under 10 bar of H2, 3 mol% of this catalyst achieved the reaction within a single hour on a 5 mmol/0.8 g substrate scale with a yield of 96 %, a turnover number (TON) of 32 and a turnover frequency (TOF) of 32. Characterizations confirmed the coordination of the NHC-olefin ligands to the nickel nanoparticles, the reduced state of the nickel and the (poly-) crystallinity of the nanoparticles.
Keywords: alkenes; Alkynes; heterocycles; Hydrogenation; imines; N -heterocyclic carbene ligand; nanocatalysis; Nickel

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.

Unveiling the reactivity of N-heterocyclic methylene hydrazines - Balayan, Kajal; Biswas, Arindam; Sharma, Himanshu; Tiwari, Prabhakar; Vanka, Kumar; Gonnade, Rajesh G.; Rath, Arup K.; Sen, Sakya S. (Dalton Transactions, 2026)
We present the first reactivity profile of N-heterocyclic methylene hydrazines, revealing distinct competition between steric and electronic control. Reactions with HCl are electronically driven, resulting in protonation at the proximal nitrogen, while the bulky Lewis acid B(C6F5)3 coordinates to the sterically accessible distal nitrogen. Additionally, we demonstrate that these scaffolds undergo spontaneous, base-free HCN elimination with tetracyanoethylene (TCNE) to form highly conjugated molecules with significantly reduced HOMO-LUMO gaps.